100 Jahre Hautklinik Erlangen - Leistner, Luise; Sticherling, Michael; Berking, Carola; Leven, Karl-Heinz (Aktuelle Dermatologie, 2024)
The appointment of Leo Hauck as the first chairman in March 1924 marks the 100 th anniversary of the establishment of university dermatology in Erlangen. This article provides an overview of the development of dermatovenerology in Erlangen from the beginning of the 20 th century to the present day. The difficult founding years were followed by stable development, which came to an abrupt end in 1945 with the death of its founder and the confiscation of the hospital by the US-American forces after the Second World War. It was not until the 1970s that the Erlangen department returned to the circle of German university dermatology. Today it is a modern research facility that ensures patient care at the highest level.
CRIS-Team Scopus Importer:2025-07-10
Keywords: Hautklinik Erlangen; Leo Hauck; Leo Hauck; Moulagen; Otto Paul Hornstein

100 Jahre Universitätshautklinik in Erlangen: Ein Beispiel für die Emanzipierung des Faches Dermatologie - Sticherling, Michael; Berking, Carola (Aktuelle Dermatologie, 2024)
CRIS-Team Scopus Importer:2025-04-01

1,064-nm diode laser therapy of onychomycosis: results of a prospective open treatment of 82 toenails - Renner, Regina; Gruesser, Kathrin; Sticherling, Michael (Dermatology, 2015)
Onychomycosis is one of the most prevalent nail disorders in adults, where conventional topical therapy is often protracted and in most cases ineffective. On the other hand, systemic/oral therapy is not suitable for all patients and might be associated with relevant side effects. Therefore, laser therapy can be used as an alternative to or extension of existing treatment protocols.We used diode laser treatment for onychomycosis to evaluate the efficacy of this treatment as single therapy as well as in combination with an ongoing antimycotic treatment.We used a 1,064-nm diode laser (FOX Laser, ARC Laser GmbH, Germany) in pulse mode with a spot size of 4 mm. The laser's settings were: 8 W, with a pulse duration of 80 ms and a repetition rate of 5.6 Hz; the energy fluence/pulse was 5.1 J/cm(2), and a total energy of 250-500 J for large and/or thickened nails (digit I), 120-200 J for medium nails (digits II-IV) and 60-120 J for small and/or very thin nail plates (digit V) was counted in the laser display. Two to three passes where applied continuously over the entire area of the nail (nail plate, nail folds and eponychium) in a grid pattern. Eighty-two affected toenails were treated at least twice every 8 weeks; all nails treated were clinically diagnosed as onychomycosis. The evaluation of the treated nails was conducted by two dermatologists, initially by semiquantitative visual examination, followed by evaluation with the Onychomycosis Severity Index (OSI). In addition, the patients were asked to state their satisfaction with the treatment and its results in a written questionnaire.All nails showed an improvement ranging between 14 and 56% including the analytical evaluation scale (OSI). Two dermatologists evaluated 34 nails. Both reported significant improvement and/or good clinical improvement, which corresponds to about 41% for both evaluations. The mean OSI of all patients was 18.9/19.9 before treatment which changed to 14.3/14.8 after treatment. This corresponds to an improvement of about 25% (-4.6/-5.1) compared to the initial value. Specifically the subgroup with positive antimycotic culture and no additional antimycotic treatment showed an improvement of about 25%. This improvement can be attributed to the effect of the diode laser treatment. When evaluating the OSI of all nails, it appears that about 15-20% of the severe OSIs improved and changed to a moderate level, while a similar portion of patients with moderate onychomycosis improved to mild onychomycosis. Patient satisfaction was measured to an average value of 4.6 out of a maximum of 10 points. About 60% of the treated patients would recommend the treatment to their family members or friends.This investigation demonstrated that diode laser treatment of onychomycosis provides acceptable results with minimal to no side effects. Further clinical evaluations could help to establish better therapy protocols, especially for those patients who had no benefit from the laser treatment, or could also be used as an add-on to an existing therap
EVALuna2:19549

50-year-old woman with cold-associated attacks of white discoloration of individual fingers: Preparation for the specialist examination: part 51 50/w mit kälteabhängiger, anfallsweiser Weißverfärbung einzelner Finger: Vorbereitung auf die Facharztprüfung: Folge 51 - Sticherling, Michael (Hautarzt, 2019)
CRIS-Team Scopus Importer:2019-05-02

50-year-old Woman with cold-associated attacks of White Discoloration of individual Fingers Preparation for the Specialist Examination: Part 51 - Sticherling, Michael (Hautarzt, 2019)
CRIS-Team WoS Importer:2019-05-03

A comparative analysis of articular bone in large cohort of patients with chronic inflammatory diseases of the joints, the gut and the skin - Simon, David; Kleyer, Arnd; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Kocijan, Roland; Haschka, Judith; Hirschmann, Simon; Atreya, Raja; Neurath, Markus; Sticherling, Michael; et al. (Bone, 2018)
Chronic inflammatory diseases are associated with bone loss. While the occurrence of systemic bone loss is well described in chronic inflammatory diseases, the impact of these conditions on articular bone has not been systematically investigated. Recent refinements in high-resolution CT assessment of the joints now allow the accurate measure of articular bone composition. In this study 476 subjects comprising healthy individuals and patients with anticitrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), ACPA-negative RA, Crohn's disease (CD), ulcerative colitis (UC), psoriasis (PsO) and psoriatic arthritis (PsA) were subjected to high-resolution quantitative computed tomography (HR-pQCT) of the hand. Metacarpal heads were assessed for total, trabecular and cortical volumetric bone mineral density (vBMD). Only ACPA+RA, but not the remaining inflammatory diseases (ACPA-RA, CD, UC, PsO, PsA) showed significant (p < 0.001) loss of articular bone affecting both the trabecular and the cortical compartments. Age and body mass index were also associated with articular bone changes, the former with lower, the latter with higher articular bone mass. In multivariate models, presence of ACPA+RA was an independent factor for articular bone loss. Among chronic inflammatory diseases ACPA+RA is the most potent precipitator for articular bone loss pointing out the role of autoimmunity in the development of articular bone disease in the context of chronic inflammatory disease.
EVALuna2:34480

Advanced neural networks for classification of MRI in psoriatic arthritis, seronegative, and seropositive rheumatoid arthritis - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Rheumatology, 2022)
Objectives: To evaluate whether neural networks can distinguish between seropositive rheumatoid arthritis (RA), seronegative RA and psoriatic arthritis (PsA) based on inflammatory patterns from hand MRI and to test how psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet neural networks were utilized to compare (i) seropositive RA vs. PsA, (ii) seronegative RA vs. PsA and (iii) seropositive vs. seronegative RA with respect to hand MRI data. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without presentation of demographic and clinical parameters. Additionally, the trained networks were applied to psoriasis patients without clinical arthritis. Results: MRI scans from 649 patients (135 seronegative RA, 190 seropositive RA, 177 PsA, 147 psoriasis) were fed into ResNet neural networks. AUROC was 75% for seropositive RA vs. PsA, 74% for seronegative RA vs. PsA and 67% for seropositive vs. seronegative RA. All MRI sequences were relevant for classification, however, when deleting contrast agent-based sequences the loss of performance was only marginal. The addition of demographic and clinical data to the networks did not provide significant improvements for classification. Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that a PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Neural networks can be successfully trained to distinguish MRI inflammation related to seropositive RA, seronegative RA, and PsA.
Keywords: Rheumatoid arthritis; Psoriatic arthritis; neural networks; deep learning

Advancement and independent validation of a deep learning-based tool for automated scoring of nail psoriasis severity using the modified nail psoriasis severity index - Kemenes, Stephan; Liu, Chang; Schlereth, Maja; Noversa de Sousa, Rita; Minopoulou, Ioanna; Fenzl, Pauline; Corte, Giulia; Yalcin-Mutlu, Melek; Höner, Michael; Sagonas, Ioannis; Coppers, Birte; Liphardt, Anna-Maria; et al. (Frontiers in Medicine, 2025)
Objective: To improve and validate a convolutional neural network (CNN)-based model for the automated scoring of nail psoriasis severity using the modified Nail Psoriasis Severity Index (mNAPSI) with adequate accuracy across all severity classes and without dependency on standardized conditions. Methods: Patients with psoriasis (PsO), psoriatic arthritis (PsA), and non-psoriatic controls including healthy individuals and patients with rheumatoid arthritis were included for training, while validation utilized an independent cohort of psoriatic patients. Nail photographs were pre-processed and segmented and mNAPSI scores were annotated by five expert readers. A CNN based on Bidirectional Encoder representation from Image Transformers (BEiT) architecture and pre-trained on ImageNet-22k was fine-tuned for mNAPSI classification. Model performance was compared with human annotations by using area under the receiver operating characteristic curve (AUROC) and other metrics. A reader study was performed to assess inter-rater variability. Results: In total, 460 patients providing 4,400 nail photographs were included in the training dataset. The independent validation dataset included 118 further patients who provided 929 nail photographs. The CNN demonstrated high classification performance on the training dataset, achieving mean (SD) AUROC of 86% ± 7% across mNAPSI classes. Performance remained robust on the independent validation dataset, with a mean AUROC of 80% ± 9%, despite variability in imaging conditions. Compared with human annotation, the CNN achieved a Pearson correlation of 0.94 on a patient-level, which remained consistent in the validation dataset. Conclusion: We developed and validated a CNN that enables the automated, objective scoring of nail psoriasis severity based on mNAPSI with high reliability and without need of image standardization. This approach has potential clinical utility for enabling a standardized time-efficient assessment of nail involvement in the psoriatic disease and possibly as a self-reporting tool.
Created from Fastlane, Scopus look-up
Keywords: artificial intelligence; machine learning; MNAPSI; nail disease; NAPSI; outcome measures; psoriasis; psoriatic arthritis

Alopecia areata- Clinical Picture and Therapy Response of Heterogeneous Disease - Busch, D.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

A matter of perspective: Imputation methods and their effects illustrated with the use of data from the PRIME study - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34782

Analyses of association of psoriatic arthritis and psoriasis vulgaris with functional NCF1 variants - Löhr, Sabine; Ekici, Arif Bülent; Uebe, Steffen; Büttner, Christian; Köhm, Michaela; Behrens, Frank; Böhm, Beate; Sticherling, Michael; Schett, Georg; Simon, David; Mössner, Rotraut; Nimeh, Ali; et al. (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-07-02

Analysis of periarticular bone changes in patients with cutaneous psoriasis without associated psoriatic arthritis - Simon, Dominic; Faustini, F.; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, R.; Haschka, Judith; Finzel, Stephanie; Kraus, Sebastian; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, J. (Annals of the Rheumatic Diseases, 2016)
To search for structural bone changes in the joints of psoriasis patients without psoriatic arthritis (PsA).55 psoriasis patients without any current or past symptoms of arthritis or enthesitis and 47 healthy controls were examined by high-resolution peripheral quantitative CT scans of the metacarpophalangeal joints. Number, size and exact localisation of erosions and enthesiophytes were recorded by analysing axial scans of the metacarpal heads and phalangeal bases and were confirmed in additional coronal and/or sagittal sections. In addition, we collected demographic and clinical data including subtype, duration and severity of psoriasis.Psoriasis patients showed a larger and significantly increased number of enthesiophytes (total number 306; mean±SD/patient 5.62±3.30) compared with healthy controls (total number 138; mean±SD/patient 3.04±1.81, p<0.001). Enthesiophytes were typically found at the dorsal and palmar sides of the metacarpal heads where functional entheses related to extensor and flexor tendons are localised. Bone erosions were rare and not significantly different between psoriasis patients and healthy controls. If present, erosions were almost exclusively found at the radial side of the second metacarpal head in both psoriasis patients and healthy controls.Psoriasis patients without PsA show substantial signs of enthesiophyte formation compared with healthy controls. These changes represent new bone formation at mechanically exposed sites of the joint and substantiate the concept of the existence of a 'Deep Koebner Phenomenon' at enthesial sites in psoriasis patients.
EVALuna2:13130

Analysis of the German Compassionate Use Program on spesolimab in patients with generalized pustular psoriasis: evidence outside of clinical trials - Krefting, Frederik; Welzel, Julia; Thamm, Janis; Thölken, Karisa; Wohlrab, Johannes; Müller, Valentina Laura; Kreuter, Alexander; Rueff, Franziska; Sticherling, Michael; Hölsken, Stefanie; Placke, Jan Malte; Sondermann, Wiebke (European Journal of Dermatology, 2024)
Background: Generalized pustular psoriasis (GPP) is a potentially life-threatening orphan disease. Interleukin (IL)-36 is a known pathogenetic key driver of GPP. The IL-36 receptor inhibitor spesolimab has shown efficacy and safety in clinical trials. However, evidence for spesolimab outside of clinical trials is limited. Objectives: To provide additional evidence for the use of spesolimab beyond clinical trials, we evaluated individual patient data as part of the spesolimab Compassionate Use Program (CUP) for GPP patients in Germany. Materials & Methods: Adult patients with an acute GPP flare received 900 mg spesolimab intravenously at baseline and received a second dose on day 8. Data on demographics, efficacy and adverse events were collected from participating sites at baseline, on day 8 and at four weeks. Results: The database included datasets from 12 GPP patients. At baseline, 72% of patients with complete data regarding efficacy (n=7) had a GPPGA (Generalized Pustular Psoriasis Physician Global Assessment) of ≥3, and all patients a PS (pustulation subscore) of ≥3. On day 8, 43% of patients had a GPPGA ≤1 and 72% a PS ≤1. After four weeks, all patients had a GPPGA ≤1 and 86% a PS ≤1. No drug-related adverse events were reported. Conclusion: These findings confirm the results of international, randomized clinical trials in a real-world setting. As spesolimab is no longer available in Germany, this study provides important information that cannot be replicated in this country.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Generalized pustular psoriasis; spesolimab

Anatomical pattern of entheseal and synovial fibroblast activation in patients with psoriasis and its risk of developing psoriatic arthritis - Corte, Giulia; Atzinger, Armin; Temiz, Selahattin Alp; Noversa de Sousa, Rita; Mutlu, Melek Yalcin; Schönau, Verena; Raimondo, Maria Gabriella; Kleyer, Arnd; Kuwert, Torsten; Ramming, Andreas; Simon, David; Sticherling, Michael; et al. (RMD Open, 2024)
OBJECTIVES: To assess the presence and anatomical distribution of activated fibroblasts in the joints and entheses of patients with psoriasis with arthralgia and to test how fibroblast activation visualised by 68gallium-labelled fibroblast activation protein inhibitor-04 (68Ga-FAPI-04)-positron emission tomography (PET)/CT correlates with clinical tenderness, musculoskeletal ultrasound findings and progression to psoriatic arthritis (PsA). METHODS: We conducted a prospective cohort study in patients with psoriasis and arthralgia who underwent clinical and ultrasound evaluation and whole-body PET/CT imaging with 68Ga-FAPI-04. 68Ga-FAPI-04 uptake at synovial and entheseal sites was assessed by maximal standardised uptake values (SUVmax) and PET/CT Joint Index (JI); logistic regression models were used to investigate its correlation with clinical and ultrasound findings. Survival analyses were performed on patients with at least 6 months of follow-up. RESULTS: 36 patients with psoriasis were enrolled. 68Ga-FAPI-04 uptake was found in 318 (7.9%) joints and 369 (7.3%) entheses in 29 (80.6%) participants, with a mean SUVmax (SD) of 3.2 (1.8) for joints and 2.9 (1.6) for entheses. Large joints and the lower limbs were predominantly affected. A significant positive relationship was found between 68Ga-FAPI-04-PET/CT signal intensity and the 68 tender joint count (SUVmax: p<0.001; PET/CT-JI: p<0.001) and tender entheses count (SUVmax: p<0.001; PET/CT-JI: p=0.002). No correlations were found with ultrasound findings (SUVmax: p=0.969; PET/CT-JI: p=0.720). Patients with relevant synovio-entheseal 68Ga-FAPI-04 uptake showed a statistically significant higher risk of developing PsA (p=0.02), independent of ultrasound findings. CONCLUSIONS: Patients with psoriasis presenting with arthralgia show localised signs of resident tissue activation in joints and entheses, which are associated with higher risk of developing PsA.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Fibroblasts; Outcome Assessment; Health Care; Psoriatic Arthritis; Risk Factors; Ultrasonography

Assessment of the Severity of Atopic Dermatitis by Physicians and Patients depending on Gender: Results from the German Atopic Dermatitis Registry TREATgermany - Heinrich, L.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder,; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Wiemers, F.; Ertner, K.; Schaekel, K.; Augustin, M.; et al. (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Association analyses of functional NCF1 variants in psoriatic arthritis and psoriasis vulgaris - Hüffmeier, Ulrike; Löhr, Sabine; Ekici, Arif Bülent; Uebe, S.; Koehm, M.; Behrens, F.; Boehm, B.; Sticherling, Michael; Schett, Georg; Moessner, R.; Nimeh, A.; Assmann, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Association of Fabry Disease and Psoriasis - therapeutically significant? - Sollfrank, Lukas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Association of Structural Entheseal Lesions With an Increased Risk of Progression From Psoriasis to Psoriatic Arthritis - Simon, David; Tascilar, Koray; Kleyer, Arnd; Bayat, Sara; Kampylafka, Eleni; Sokolova, Maria; Zekovic, Ana; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, Klaus; Sticherling, Michael; et al. (Arthritis and Rheumatology, 2021)
Objective. To test whether the presence of structural entheseal lesions in psoriasis patients influences the risk of progression to psoriatic arthritis (PsA).
CRIS-Team WoS Importer:2022-01-07

Author Correction: DeepNAPSI multi-reader nail psoriasis prediction using deep learning. - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Simon, David; Minopoulou, Ioanna; Sticherling, Michael; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Scientific Reports, 2023)
EVALuna2:538275

A yet undescribed IRF6 variant causes a new type of ectodermal dysplasia with natal teeth - Peschel, Nicolai; Willershausen, Ines; Schliep, Stefan; Sticherling, Michael; Schneider, Holm (Journal of the European Academy of Dermatology and Venereology, 2025)
CRIS-Team Scopus Importer:2025-02-14

Bäckerasthma bei der Lakritzherstellung? - Azem, Tara; Sticherling, Michael; Berking, Carola; Wagner, Nicola (Aktuelle Dermatologie, 2024)
Bakers are at high risk of developing occupational rhinoconjunctivitis and asthmatic symptoms. The so-called baker's asthma is a form of occupational allergic asthma, which is typically triggered by grain or flour dust as a workplace-related inhalant allergen. A specific medical history enables the classification of workplace-related respiratory exposure to occupational risks. In addition, the diagnosis of baker's asthma requires thorough allergy diagnostics through prick testing and serological determination of specific IgE antibodies to detect a type I sensitization to occupational inhalant allergens, as well as lung function tests. Early diagnosis and identification of the triggering inhalant allergen are important to favorably influence the prognosis by the timely initiation of measures to avoid exposure. In the following, we present the case of a 30-year-old trained baker who developed occupational asthmatic symptoms first during production of liquorice sweets that necessitated a transfer within the company.
CRIS-Team Scopus Importer:2025-04-01
Keywords: allergy; Berufskrankheit; liquorice; occupational asthma; occupational disease

Baseline characteristics, disease severity and treatment history of patients with atopic dermatitis included in the German AD Registry TREATgermany - Heratizadeh, A.; Haufe, E.; Stoelzl, D.; Abraham, S.; Heinrich, L.; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Augustin, M.; Wiemers, F.; Zink, A.; Von Kiedrowski, R.; et al. (Journal of the European Academy of Dermatology and Venereology, 2020)
Background The Atopic Dermatitis (AD) TREATgermany registry was initiated by the German Society for Dermatology (DDG) in 2011 to evaluate the 'real-life' situation of health care for patients with AD.
CRIS-Team WoS Importer:2020-02-28

B-cells in psoriasis? - Banki, Simon; Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Behandlung der Psoriasis mit Secukinumab: Praxisrelevante Hinweise - Körber, Andreas; Augustin, Matthias; Behrens, Frank; Gerdes, Sascha; von Kiedrowski, Ralph; Schäkel, Knut; Sticherling, Michael; Wilsmann-Theis, Dagmar; Wohlrab, Johannes; Simon, Jan Christoph (Hautarzt, 2021)
Background: Moderate to severe plaque psoriasis can be treated effectively with immunomodulating biologicals such as the interleukin-17A inhibitor secukinumab. In practice, however, questions often arise as to how to proceed in special situations, such as infections, comorbidity, pregnancy, or surgery. Objectives: To address frequent questions about the treatment of plaque psoriasis with secukinumab in a consensus document of German psoriasis experts that supplements current guidelines. Methods: In a virtual expert meeting in May 2020, practical aspects of the treatment of psoriasis were discussed based on the experience of the participants and on current literature. The results of this discussion were summarized in the present consensus document. Results: This article provides practical guidance on case history, documentation of previous therapies, severity of psoriasis, and comorbidities before starting therapy with secukinumab. For patients treated with secukinumab, the course of action in case of vaccinations, chronic or acute infections, surgical interventions, special manifestations of psoriasis, and comorbidities including history of cancer and autoimmune disorders is discussed. Questions regarding family planning and health policy regulations are also addressed. Discussion: The recommendations for the treatment of psoriasis with secukinumab summarized in this consensus document may contribute to achieve optimal therapy for patients and to improve their quality of life.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Biological products; Comorbidity; Infections; Perioperative management; Special situations

Beyond-Mild Psoriasis: A Consensus Statement on Calcipotriol and Betamethasone Dipropionate Foam for the Topical Treatment of Adult Patients - Aschoff, Roland; Bewley, Anthony; Dattola, Annunziata; De Simone, Clara; Lahfa, Mourad; Llamas-Velasco, Mar; Martorell, Antonio; Pavlovic, Mira; Sticherling, Michael (Dermatology and Therapy, 2021)
Introduction There are clear treatment options for mild psoriasis where topical therapies are the mainstay, and for severe psoriasis where systemic therapy (biologic or non-biologic) is necessary. However, there is less clarity in the 'grey zone' of patients in the moderate or so-called 'beyond-mild' segment. There are frequent delays to the initiation, discontinuation, switching and dose change in treatment, and many patients fail to continue treatment because of concerns about safety or lack of efficacy. Treatment with topical therapies, such as calcipotriol and betamethasone dipropionate (Cal/BD) combinations, may be suitable for these patients. Method These consensus recommendations on the use of topical therapies including Cal/BD foam for beyond-mild psoriasis originated from a modified Delphi process of European clinical experts. In the process, the experts iteratively refined a series of draft statements, which had to receive >= 80% approval to be incorporated into the consensus. Results The experts identified three main themes: Cal/BD foam as monotherapy, as an add-on to non-biologic systemic therapies and as an add-on to systemic biologics. The consensus emphasises disease factors and patient preference in treatment choice, summarises the evidence base for Cal/BD foam monotherapy for flare treatment as well as long-term management, and identifies the potential for improved treatment outcomes, such as reduced time to onset of action and reduced systemic dose to minimise side effects for add-on Cal/BD therapy to non-biologic systemics. The recommendations regarding add-on Cal/BD foam to biologics are similar to those for non-biologic systemic therapies, but also include suggestions for patients on biologics who are late responders. As clinical choices of Cal/BD combination vary, we have here often used 'Cal/BD' without reference to any particular formulation. Conclusions These recommendations aim to give practical guidance to those treating patients with beyond-mild psoriasis, to support patients' use of topical preparations and to optimise treatment outcomes.
CRIS-Team WoS Importer:2021-09-24

Blood-Based Biomarkers of Inflammation and Tissue Remodeling Can Discriminate Between Rheumatoid Arthritis, Psoriasis, and Psoriatic Arthritis and Are Associated with Hand Function - Port Linares, Helena; Coppers, Birte; Bayat, Sara; Godonou, Elie-Tino; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne-Christine; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Heinrich, Simon; et al. (poster, American College of Rheumatology Convergence, 2023)

Bone microstructure and volumetric bone mineral density in patients with hyperuricemia with and without psoriasis - Simon, David; Haschka, J.; Muschitz, C.; Kocijan, A.; Baierl, A.; Kleyer, Arnd; Schett, Georg; Kapiotis, S.; Resch, H.; Sticherling, Michael; Rech, Jürgen; Kocijan, R. (Osteoporosis international, 2020)
Summary: We analyzed volumetric bone mineral density (vBMD) and bone microstructure using HR-pQCT in subjects with normouricemia (NU) and subjects with hyperuricemia (HU) with and without psoriasis (PSO). HU was associated with higher cortical vBMD and thickness. Differences in average and trabecular vBMD were found between patients with PSO + HU and NU. Introduction: Hyperuricemia (HU) and gout are co-conditions of psoriasis and psoriatic arthritis. Current data suggest a positive association between HU and areal bone mineral density (BMD) and a negative influence of psoriasis on local bone, even in the absence of arthritis. However, the influence of the combination of HU and psoriasis on bone is still unclear. The aim of this study was to assess the impact of HU with and without psoriasis on bone microstructure and volumetric BMD (vBMD). Methods: Healthy individuals with uric acid levels within the normal range (NU), with hyperuricemia (HU), patients with hyperuricemia and psoriasis (PSO + HU), and patients with uric acid within the normal range and psoriasis (PSO + NU) were included in our study. Psoriasis patients had no current or past symptoms of arthritis. Average, trabecular, and cortical vBMD (mgHA/cm3); trabecular number (Tb.N, 1/mm) and thickness (Tb.Th, mm); inhomogeneity of the network (1/N.SD, mm); and cortical thickness (Ct.Th., mm) were carried out at the ultradistal radius using high-resolution peripheral quantitative computed tomography. In addition, bone turnover markers such as DKK-1, sclerostin, and P1NP were analyzed. Results: In total, 130 individuals were included (44 NU participants (34% female), 50 HU (24%), 16 PSO + HU (6%), 20 PSO + NU (60%)). Subjects were aged: NU 54.5 (42.8, 62.1), HU 57.5 (18.6, 65.1), PSO + HU 52.0 (42.3, 57.8), and PSO + NU 42.5 (34.8, 56.8), respectively. After adjusting for age, sex, BMI, and diabetes, patients in the HU group revealed significantly higher values of cortical vBMD (p < 0.001) as well as cortical thickness (p = 0.04) compared to the NU group. PSO + NU showed no differences to NU, but PSO + HU demonstrated both lower average (p = 0.03) and trabecular vBMD (p = 0.02). P1NP was associated with average, cortical, and trabecular vBMD as well as cortical thickness while sclerostin levels were related to trabecular vBMD. Conclusion: Hyperuricemia in otherwise healthy subjects was associated with a better cortical vBMD and higher cortical thickness. However, patients with both psoriasis and hyperuricemia revealed a lower vBMD.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Bone Mineral Density; HR-pQCT; Hyperuricemia; Psoriasis

Bone Microstructure in Patients with Cutaneous Psoriasis and No History of Psoriatic Arthritis Shows Bone Anabolic Changes at a Greater Extent Than in Healthy Controls - Simon, David; Faustini, Francesca; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, Roland; Haschka, Judith; Finzel, Stephanie; Kraus, Sebastian; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2014)
EVALuna2:13229

Case report: Bullous pemphigoid in HIV-1-positive patients: interplay or coincidence? A case series and review of the literature - Foerster, Yannick; Sollfrank, Lukas; Rechtien, Laura; Harrer, Thomas; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune inflammatory skin disease, mostly affecting the elderly population. Therefore, patients often have multiple comorbidities, but there is inconsistent data regarding the relationship between HIV-1 infection and BP, which has been rarely reported in combination. Herein, we describe three patients who presented with BP and concomitant HIV-1 infection that was well controlled with modern combined antiretroviral therapy. All patients received topical and oral corticosteroids. Depending on the individual severity, further add-on therapeutics, such as azathioprine, dapsone, doxycycline and the interleukin 4/13 antibody dupilumab, were added to the therapy regimen. All patients recovered from pruritic skin lesions and blistering. The cases are further discussed in the context of the current study landscape. In conclusion, HIV-1 infection shifts the cytokine profile from T-helper type 1 (TH1) towards T-helper type 2 (TH2), resulting in the excessive secretion of distinct cytokines, such as interleukin 4 (IL-4) and interleukin 10 (IL-10). With IL-4 being a main driver in the pathogenesis of BP, HIV-1-positive patients may benefit greatly from targeting IL-4 with monoclonal antibodies.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aids; bullous pemphigoid; COVID-19; dupilumab; HIV-1; immune reconstitution inflammatory syndrome; iris

Case Report: The many faces of bullous pemphigoid - Rechtien, Laura; Sollfrank, Lukas; Foerster, Yannick; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
The pemphigoid group comprises a number of bullous skin diseases with autoantibodies against different constituents of the basement membrane zone that result in subepidermal detachment and clinically characteristic tense blisters, erosions, urticarial erythema, and itching. Apart from the most frequent type of bullous pemphigoid with antibodies against BP180, which is found predominantly in elderly patients, the disease may present at other ages and different pathogenic conditions. Here, four cases are presented of young age (3 months and 25, 34, and 46 years) and in association with vaccination, pregnancy, or metastatic cancer. Though anti-BP180 was found in all cases, a different pathogenic background may be found in any of them, resulting in characteristic clinical manifestation, yet demanding specifically adapted therapeutic approaches.
CRIS-Team Scopus Importer:2023-11-03
Keywords: bullous autoimmune disease; bullous pemphigoid; COVID-19 vaccination; juvenile pemphigoid; pemphigoid gestationis

CD163/CD63+ Monocyte-Derived DC Profiled in Tissue by Multi-Antigen Analysis (MAA) Discriminate Chronic Eczema and Psoriasis - Windorfer, Sabrina; Kirr, Michael; Fröhlich, Waltraud; Plosnita, Bianca; Ostalecki, Christian; Berking, Carola; Sticherling, Michael; Baur, Andreas (International Journal of Molecular Sciences, 2025)
Psoriasis (Pso) is a chronic inflammatory skin disease with a genetic predisposition and an assumed autoimmune pathomechanism. Autoantigens, dendritic cells (DCs), and the TNF/IL23/Il17 axis are seemingly the main drivers of this process. However, the difference to other DC-driven immune processes, like in eczematic skin, is insufficiently understood. Multi-antigen analysis (MAA) allows the staining of tissue with 100 antigens and more and provides a deeper insight into pathological processes, using advanced imaging analysis and quantification of topographical allocated processes. Here we used this technology to assess and compare the skin immune infiltrations in Pso, chronic eczema, and healthy controls. Tissue samples from both skin diseases (n = 30) were stained for 63 antigens, including 45 immune markers, and cells were analysed and quantified in both epidermis and dermis. The presence of different types of monocyte-derived DC in the epidermis was the most notable distinction between both skin diseases. While in Pso a monocyte-derived DC (CD14+CD1a+CD11c+) predominated, possibly a Langerhans cell (LC)-like DC, eczema displayed a marker combination of a seemingly more differentiated monocyte-derived DC (CD14+CD63+CD163+), potentially a DC3 cell type.
CRIS-Team Scopus Importer:2025-10-03
Keywords: atopic dermatitis; DC; DC3 cells; eczema; inflammatory dendritic cells; Langerhans cells; multi-antigen analysis; multiplex imaging; psoriasis

CHRONIC TENOSYNOVITIS IS ASSOCIATED WITH LOSS OF GRIP STRENGTH IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS (OP0069) - Bayat, Sara; Coppers, Birte; Kleyer, Arnd; Godonou, Elie-Tino; Valor, L.; Simon, David; Fagni, Filippo; Corte, Giulia; Schönau, Verena; Tascilar, Koray; Hueber, Axel; Sticherling, Michael; et al. (Annals of the Rheumatic Diseases, 2023)
Background Rheumatic diseases result in joint destruction and impaired physical function [1]. We recently showed, that hand function based on objective tests may serve as a biomarker representing subclinical inflammation in psoriasis (Pso) patients and thus could support the early detection of psoriatic arthritis (PsA) onset [2]. Hand function tests are relevant for objective assessment of musculoskeletal function in relation to disease activity in PsA [3], However, the relationship of hand function with the synovitis and tenosynovitis detected by ultrasound (US) in PsA and Pso patients has not been well studied. Objectives To investigate the association of synovitis and tenosynovitis detected by US in greyscale (GS) and power doppler (PD) activity with grip strength and fine motor skills in patients with PsA and Pso. Methods PsA and Pso patients were recruited from the Rheumatology Department at the University Hospital erlangen, for this cross-sectional study. After giving written informed consent, subject characteristics were recorded and study participants underwent bilateral US of the wrists, metacarpophalangeal (MCP) joints, and flexor tendons of all fingers. Each joint was examined by GS (0-3), PD (0-3) and finally a combined score (PDUS: PD + GS) was calculated (0-3) [4]. The flexor tendon was scanned in GS (0/1) and with PD [0-3]. US activity considered either a synovitis or tenosynovitis score ≥1. Activity in tender joint count (TJC) and swollen joint count (SJC) 68/66 was considered ≥1 tender or ≥1 swollen joint. Hand function was assessed by vigorimetric grip strength (lbf) and the fine motor skill MPUT (Moberg pick-up test). For the analysis, patients’ hands were either divided in dominant/non-dominant or patient reported affected/non-affected hand. A correlation matrix was applied to measure the linear relation between the pairs of synovitis and tenosynovitis scores, grip strength and MPUT for both hands, using the Spearman correlation method. Results 106 patients (40 PsA, 66 Pso) participated in this study. Subject characteristics and general outcomes are summarized in Table 1. While grip strength was higher in the dominant hand (p<0.001), MPUT times are comparable between the dominant vs. non-dominant hands (p=0.056) but was faster in the non-affected hand (p=0.008). Low to moderate positive correlations were observed between both, overall GS synovitis score (MCP 2-5 + wrist) (r=0.24, p<0.05), and PDUS (r=0.23, p<0.05) with MPUT. In US active patients, a high correlation between grip strength and GS tenosynovitis score in digit 2 (r=-0.566, p=0.028) was detected. When considering patients with US in addition to SJC/TJC activity, imaging modalities did not correlate with hand function. Conclusion These findings indicate that the synovitis detected by greyscale is related with fine motor skills and tenosynovitis in greyscale with grip strength. This suggests, that chronic tenosynovitis has a greater impact on hand function than the acute inflammatory phase. When considering patients with TJC68/SJC66 ≥1 this relation is not present, suggesting that clinically assessed joint count, unlike ultrasonography, does not correlate with hand function impairmen

Chronische Entzündungserkrankungen in Deutschland: Eine Querschnittanalyse über Begleiterkrankungen und Arzneimitteleinsatz - Leipe, Jan; Schmelz, Renate; Riemekasten, Gabriela; Thaçi, Diamant; Henes, Jörg; Schäkel, Knut; Pinter, Andreas; Sticherling, Michael; Wegner, Joanna; Fusco, Stefano; Linke, Miriam; Weber, Valeria; et al. (Zeitschrift für Rheumatologie, 2023)
Background: Immune-mediated inflammatory diseases (IMID) can lead to a substantial disease burden for those affected, in particular by the concomitant occurrence of other IMIDs or in the presence of comorbidities. The care of patients with IMIDs is complex and involves various medical disciplines. Objective: To describe the burden of disease and the current routine drug treatment of patients with IMID. Material and methods: The retrospective cross-sectional analysis was based on statutory health insurance claims data from the InGef database. Prevalent patients with psoriasis (Pso), psoriatic arthritis (PsA), spondylarthritis (SpA), rheumatoid arthritis (RA), Crohn’s disease (MC), ulcerative colitis (CU), or connective tissue disease were identified among 3,988,695 insured patients in 2018. The concomitant occurrence of different IMIDs and the extent to which patients with IMID are affected by other comorbidities compared to a reference population were investigated. The current routine drug treatment was described based on the use of predefined forms of treatment. Results: In the database 188,440 patients with IMID (4.7%) were identified. Compared to the reference population the prevalence of comorbidities, such as depressive episodes and cardiovascular risk factors was higher in patients with IMID. For MC, CU, RA, and PsA disease-modifying antirheumatic drugs (DMARD) and classical systemic forms of treatment were used most commonly. In Pso, SpA, and connective tissue disease nonsteroidal anti-inflammatory drugs (NSAID) were the most frequently used treatment often in combination with other drugs. Conclusion: A considerable number of patients with IMIDs (16.9–27.5%) suffer from different diseases of the IMID group. They are frequently affected by accompanying illnesses and require interdisciplinary medical treatment.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Chronic inflammatory diseases; Epidemiology; Pharmacotherapy; Real-world evidence; Statutory health insurance data analysis

CLASSIFICATION OF PSORIATIC ARTHRITIS, SERONEGATIVE RHEUMATOID ARTHRITIS, AND SEROPOSITIVE RHEUMATOID ARTHRITIS USING DEEP LEARNING ON MAGNETIC RESONANCE IMAGING - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Supplement 1, 2022)
Background: While MRI evaluation of joints has been primarily used to quantify inflammation at a cross-sectional and longitudinal level, less is known about the potential of MRI in distinguishing different patterns of inflammation in the various forms of arthritis. Objectives: To evaluate (i) whether deep learning using neural networks can be trained to distinguish between seropositive rheumatoid arthritis (RA+), seronegative RA (RA-), and psoriatic arthritis (PsA) based on structural inflammatory patterns on hand magnetic resonance imaging and (ii) to assess if psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet 3D [1] neural networks were trained to distinguish (i) RA+ vs. PsA, (ii) RA- vs. PsA and (iii) RA+ vs. RA- with respect to hand MRI data. Diagnosis of patients was determined using the following guidelines: ACR/EULAR 2010 [2] for RA and CASPAR [3] for PsA. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without imputation of demographic and clinical parameters ( Figure 1A ). Additionally, the trained networks were applied to psoriasis patients without clinical signs of PsA. Results: MRI scans from 649 patients (135 RA-, 190 RA+, 177 PsA, 147 psoriasis) were included ( Table 1 ). The AUROC for differentiation between disease entities was 75% (SD 3%) for RA+ vs. PsA, 74% (SD 8%) for RA- vs. PsA, and 67% (6%) for RA+ vs. RA-. All MRI sequences were relevant for classification, however, when deleting CE sequences, the loss of performance was only marginal. The addition of patient-specific data to the networks did not provide significant improvements. Increasing amounts of training data demonstrated improved performance of the networks ( Figure 1B ). Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Deep learning can be successfully applied to differentiate MRI inflammatory patterns related to RA+, RA-, and PsA. Early changes in psoriasis patients can be recognized by neural networks and are characterized by a pattern that allowed the networks to classify them as PsA. <
Keywords: Rheumatoid arthritis; deep learning; neural networks

Common German language nomenclature for systemic sclerosis - Aringer, Martin; Mueller-Ladner, U.; Burkhardt, H.; Distler, Jörg; Distler, O.; Graninger, W. B.; Günther, Claudia; Hunzelmann, N.; Kiener, H.; Sticherling, Michael; Sunderkoetter, C.; Walker, U. A.; et al. (Zeitschrift für Rheumatologie, 2015)
Large data bases and the projects arising from them have led to a much improved understanding of systemic sclerosis over the last decade. Serology has developed further so that more autoantibodies are available for routine testing. Capillary microscopy has become standard and relevant progress has also been made in therapy. Many diagnostic terms found in medical documentation do not adequately reflect this progress. The nomenclature is inconsistent and, therefore, confusing. The international classification of diseases (ICD) nomenclature is, from our point of view, also in need of improvement. This article aims to reestablish a common German language standard for systemic sclerosis, which reflects current knowledge and is suitable for implementation in the clinical routine.
EVALuna2:13102

COMPARISON OF BONE MICROSTRUCTURE OF PSORIATIC ARTHRITIS AND PSORIASIS PATIENTS - AN HR-PQCT STUDY OF ANABOLIC AND CATABOLIC BONE CHANGES - Simon, David; Faustini, F.; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, R.; Haschka, J.; Figueiredo, C.; Kraus, S.; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2015)
EVALuna2:34458

Consensus statement on the diagnosis and treatment of sclerosing diseases of the skin, Part 1: Localized scleroderma, systemic sclerosis and overlap syndromes - Knobler, R.; Geroldinger-Simić, M.; Kreuter, A.; Hunzelmann, N.; Moinzadeh, P.; Rongioletti, F.; Denton, C. P.; Mouthon, L.; Cutolo, M.; Smith, V.; Gabrielli, A.; Bagot, M.; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
The term ‘sclerosing diseases of the skin’ comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present consensus provides an update to the 2017 European Dermatology Forum Guidelines, focusing on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, updated strategies for the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 1 of this consensus provides clinicians with an overview of the diagnosis and treatment of localized scleroderma (morphea), and systemic sclerosis including overlap syndromes.
CRIS-Team Scopus Importer:2024-04-12

Consensus statement on the diagnosis and treatment of sclerosing diseases of the skin, Part 2: Scleromyxoedema and scleroedema - Knobler, Robert; Geroldinger-Simić, Marija; Kreuter, Alexander; Hunzelmann, Nicolas; Moinzadeh, Pia; Rongioletti, Franco; Denton, Christopher; Mouthon, Luc; Cutolo, Maurizio; Smith, Vanessa; Gabrielli, Armando; Bagot, Martine; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
The term ‘sclerosing diseases of the skin’ comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present consensus provides an update to the 2017 European Dermatology Forum Guidelines, focusing on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, updated strategies for the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 2 of this consensus provides clinicians with an overview of the diagnosis and treatment of scleromyxoedema and scleroedema (of Buschke).
CRIS-Team Scopus Importer:2024-04-12

Contrary immediate effect of abatacept on skin and joint manifestations in psoriatic arthritis - Valor-Méndez, Larissa; Kleyer, Arnd; Schett, Georg; Manger, Bernhard; Sticherling, Michael (Rheumatology, 2021)
CRIS-Team Scopus Importer:2021-11-05

Corrigendum: Advancement and independent validation of a deep learning-based tool for automated scoring of nail psoriasis severity using the modified nail psoriasis severity index (Frontiers in Medicine, (2025), 12, (1574413), 10.3389/fmed.2025.1574413) - Kemenes, Stephan; Chang, Liu; Schlereth, Maja; Corte, Giulia; Noversa de Sousa, Rita; Minopoulou, Ioanna; Fenzl, Pauline; Yalcin-Mutlu, Melek; Höner, Michael; Sagonas, Ioannis; Coppers, Birte; Liphardt, Anna-Maria; et al. (Frontiers in Medicine, 2025)
In the published article, an author name was incorrectly written as Anna-Maria Liphart. The correct spelling is Anna-Maria Liphardt. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2025-07-25
Keywords: artificial intelligence; machine learning; MNAPSI; nail disease; NAPSI; outcome measures; psoriasis; psoriatic arthritis

COVID-19 and immune-mediated inflammatory diseases: effect of disease and treatment on COVID-19 outcomes and vaccine responses - Fagni, Filippo; Simon, David; Tascilar, Koray; Schoenau, Verena; Sticherling, Michael; Neurath, Markus; Schett, Georg (The Lancet Rheumatology, 2021)
At the beginning of the COVID-19 pandemic, patients with immune-mediated inflammatory diseases were considered to be at high risk for SARS-CoV-2 infection and the development of severe COVID-19. Data collected over the past year, however, suggest that a diagnosis of inflammatory arthritis, psoriasis, or inflammatory bowel diseases does not increase risk for SARS-CoV-2 infection or severe COVID-19 compared with people without these diseases. Furthermore, substantial data suggest that certain medications frequently used in patients with immune-mediated inflammatory diseases, in particular cytokine inhibitors, might even lower the risk for severe COVID-19. Conversely, glucocorticoids and potentially B-cell-depleting treatments seem to worsen COVID-19 outcomes. Additionally, the first data on SARS-CoV-2 vaccination in patients with these diseases suggest that tolerability of vaccination in patients with immune-mediated inflammatory diseases is good, although the immune response to vaccination can be somewhat reduced in this patient group, particularly those taking methotrexate or CD20-targeted treatment.
CRIS-Team Scopus Importer:2021-10-01

COVID-19 and implications for dermatological and allergological diseases - Buhl, Timo; Beissert, Stefan; Gaffal, Evelyn; Goebeler, Matthias; Hertl, Michael; Mauch, Cornelia; Reich, Kristian; Schmidt, Enno; Schoen, Michael P.; Sticherling, Michael; Sunderkoetter, Cord; Traidl-Hoffmann, Claudia; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
COVID-19, caused by the coronavirus SARS-CoV-2, has become pandemic. A further level of complexity opens up as soon as we look at diseases whose pathogenesis and therapy involve different immunological signaling pathways, which are potentially affected by COVID-19. Medical treatments must often be reassessed and questioned in connection with this infection. This article summarizes the current knowledge of COVID-19 in the light of major dermatological and allergological diseases. It identifies medical areas lacking sufficient data and draws conclusions for the management of our patients during the pandemic. We focus on common chronic inflammatory skin diseases with complex immunological pathogenesis: psoriasis, eczema including atopic dermatitis, type I allergies, autoimmune blistering and inflammatory connective tissue diseases, vasculitis, and skin cancers. Since several other inflammatory skin diseases display related or comparable immunological reactions, clustering of the various inflammatory dermatoses into different disease patterns may help with therapeutic decisions. Thus, following these patterns of skin inflammation, our review may supply treatment recommendations and thoughtful considerations for disease management even beyond the most frequent diseases discussed here.
CRIS-Team Scopus Importer:2020-08-07

COVID-19: risk for cytokine targeting in chronic inflammatory diseases? - Schett, Georg; Sticherling, Michael; Neurath, Markus (Nature Reviews Immunology, 2020)
CRIS-Team Scopus Importer:2020-04-28

COVID-19 und Auswirkungen auf dermatologische und allergologische Erkrankungen - Buhl, Timo; Beissert, Stefan; Gaffal, Evelyn; Goebeler, Matthias; Hertl, Michael; Mauch, Cornelia; Reich, Kristian; Schmidt, Enno; Schön, Michael P.; Sticherling, Michael; Sunderkötter, Cord; Traidl-Hoffmann, Claudia; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-08-28

Crusted Nodules on the Lower Left Arm in a Traveller Returning from South America: A Quiz. Furuncular myiasis - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Sticherling, Michael (Acta Dermato-Venereologica, 2018)
EVALuna2:34409

Deepnapsi: Deep Learning for Nail Psoriasis Prediction - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Sticherling, Michael; Simon, David; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Proceedings - International Symposium on Biomedical Imaging, 2023)
Nail psoriasis is a frequent condition that is associated with a severe course of rheumatic diseases. Thus, it may be used to adapt the therapy of patients according to the change of nail psoriasis. The nail psoriasis severity index (NAPSI) was developed to measure this condition. Nevertheless, there is a lack of application for the NAPSI, as its use in the clinic is too time-consuming. In this work, we propose the use of advancements in deep learning in a new domain by recording, annotating, and predicting the NAPSI based on photographs of the hand and term our approach DeepNAPSI. This allows not just the automated recording of the NAPSI in the clinic, but also patient self-assessment from home. Our method achieved an area-under-receiver-operator-characteristic curve (AUROC) of 0.83 and 0.86 for macro and micro averaging, respectively, and a mean absolute error of 0.55.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Deep Learning; Mobile device; Nail psoriasis; Precision medicine

DeepNAPSI multi-reader nail psoriasis prediction using deep learning - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Simon, David; Minnopoulou, Ioanna; Sticherling, Michael; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Nature Scientific Reports, 2023)
Nail psoriasis occurs in about every second psoriasis patient. Both, finger and toe nails can be affected and also severely destroyed. Furthermore, nail psoriasis is associated with a more severe course of the disease and the development of psoriatic arthritis. User independent quantification of nail psoriasis, however, is challenging due to the heterogeneous involvement of matrix and nail bed. For this purpose, the nail psoriasis severity index (NAPSI) has been developed. Experts grade pathological changes of each nail of the patient leading to a maximum score of 80 for all nails of the hands. Application in clinical practice, however, is not feasible due to the time-intensive manual grading process especially if more nails are involved. In this work we aimed to automatically quantify the modified NAPSI (mNAPSI) of patients using neuronal networks retrospectively. First, we performed photographs of the hands of patients with psoriasis, psoriatic arthritis, and rheumatoid arthritis. In a second step, we collected and annotated the mNAPSI scores of 1154 nail photos. Followingly, we extracted each nail automatically using an automatic key-point-detection system. The agreement among the three readers with a Cronbach’s alpha of 94% was very high. With the nail images individually available, we trained a transformer-based neural network (BEiT) to predict the mNAPSI score. The network reached a good performance with an area-under-receiver-operator-curve of 88% and an area-under precision-recall-curve (PR-AUC) of 63%. We could compare the results with the human annotations and achieved a very high positive Pearson correlation of 90% by aggregating the predictions of the network on the test set to the patient-level. Lastly, we provided open access to the whole system enabling the use of the mNAPSI in clinical practice.

Dermatological Moulages in Germany- Comparison of Two Representative Collections - Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Dermatological Quality of Life and Neurodermatitis: Results from the German Neurodermatitis Registry TREATgermany - Helmert, C.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder, I.; Kleinheinz, A.; Wollenberg, A.; Wiemers, F.; Weisshaar, E.; Augustin, M.; Zink, A.; Von Kiedrowski, R.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Dermatology Part 2: Ichthyoses and Psoriasis - Sticherling, Michael (Handbook of Experimental Pharmacology, 2020)
Acute and chronic inflammatory skin diseases are frequent in childhood and may be hereditary or acquired. In this context, ichthyosis is rather a symptom than a defined disease as scaling is accompanying a number of disorders and is mostly consequence of a disrupted skin barrier. Ichthyosis is the basic pathogenic trait of atopic dermatitis but on the other side describes a group of rare hereditary diseases. These may only affect the skin or comprise several internal symptoms as well. Psoriasis is another scaling inflammatory skin disease with classical sharply demarcated erythematosquamous plaques and with a distinct immunogenetic background. It comprises several clinical subsets, some of which are characteristic for children and demanding in both diagnostics and therapy. Comorbid diseases point towards a systemic inflammatory response and require ample, often systemic treatment. Both ichthyosis and psoriasis may be topically treated including emollients with and without humectants as well as active agents like corticosteroids, vitamin D derivatives, and calcineurin inhibitors. In moderate to severe diseases, systemic treatment should be applied using methotrexate, ciclosporin, fumarates, or biologics. Their use should be critically discussed yet if necessary and indicated be applied to avoid chronic physical and psychological damage to the affected children.
EVALuna2:212856

Dermatomyositis- a rare, but important Disease between Dermatology and Internal Medicine - Sell, S.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Differential expression of toll like receptors and antibiotic peptides by human keratinocytes - Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (2019)
EVALuna2:212072

DISEASE INTERCEPTION IN PSORIASIS PATIENTS WITH SUBCLINICAL JOINT INFLAMMATION BY INTERLEUKIN 17 INHIBITION WITH SECUKINUMAB - DATA FROM A PROSPECTIVE OPEN LABEL STUDY - Kamoylafka, E.; Oliveira, I. D.; Linz, C.; Lerchen, V.; Englbrecht, Matthias; Simon, David; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Schett, Georg; Hueber, Axel (2018)
EVALuna2:34789

Disease interception with interleukin-17 inhibition in high-risk psoriasis patients with subclinical joint inflammation - Data from the prospective IVEPSA study - Kampylafka, Eleni; Simon, David; D'Oliveira, Isabelle; Linz, Christina; Lerchen, Veronika; Englbrecht, Matthias; Rech, Jürgen; Kleyer, Arnd; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2019)
Background: A specific subset of psoriasis patients is characterized by subclinical inflammatory changes. These patients frequently present with arthralgia and have a higher risk to develop psoriatic arthritis (PsA). We hypothesized that IL-17A inhibition in this subset of patients can intercept the link between skin and joint disease and resolves pain and inflammatory changes. Methods: Psoriasis, but no PsA, patients were included in the open prospective exploratory Interception in very early PsA (IVEPSA) study. Patients had to have nail or scalp involvement or a high psoriasis area severity index (PASI) (> 6) as well as inflammatory or erosive changes in MRI or CT. Patients received treatment with the anti-interleukin (IL)-17A antibody secukinumab over 24 weeks. Clinical assessments of skin and joint disease were done at baseline and after 12 and 24 weeks, MRI and CT at baseline and after 24 weeks. Results: Twenty patients were included, 85% of them reporting arthralgia and 40% had tender joints at the examination. Eighty-three percent had at least one inflammatory lesion in the MRI, most of them synovitis/enthesitis. Skin disease (PASI: p < 0.002; BSA: p < 0.003) and arthralgia (VAS pain: p < 0.003) significantly improved after 24 weeks. Total PsAMRIS (p = 0.005) and synovitis subscore (p = 0.008) also significantly improved. Erosions and enthesiophytes did not progress, while bone mass in the distal radius significantly (p = 0.020) increased after 24 weeks. Conclusions: These data suggest that very early disease interception in PsA is possible leading to a comprehensive decline in skin symptoms, pain, and subclinical inflammation. IVEPSA therefore provides rationale for future early interventions with the concept to prevent the onset of PsA in high-risk individuals. Trial registration: Trial registry name PSARTROS; trial registry number: NCT02483234; June 26, 2015.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Interleukin-17; Magnetic resonance imaging; Psoriasis; Psoriatic arthritis

Disseminated Pustules in a 3 Year Old Boy - Grosch, Ella; Koeceroglu, M.; Schliep, S.; Kiesewetter, Franklin; Sticherling, Michael; Voskens, C. J. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Disturbed Spatial WNT Activation—A Potential Driver of the Reticularized Skin Phenotype in Systemic Sclerosis - Chenguiti Fakhouri, Sara; Zhu, Honglin; Li, Yi Nan; Ronicke, Moritz; Rigau, Aleix Rius; Dees, Clara; Konstantinidis, Laura; Schmid, Rafael; Matei, Alexandru Emil; Eckstein, Markus; Geppert, Carol-Immanuel; Ludolph, Ingo; et al. (Arthritis and Rheumatology, 2025)
Objective: Little is known on the mechanisms necessary to maintain the physiologic adult human skin integrity. This study aims to quantitatively describe anatomic changes in systemic sclerosis (SSc)–skin compared with controls and investigate the underlying mechanisms. Methods: Skin morphology was histologically assessed in 23 patients with SSc, 18 controls, and 15 patients with hypertrophic scars. Spatial WNT/β-catenin-activation was analyzed by RNAscope and immunofluorescence staining. Enrichment of reticular marker genes in predefined fibroblast subpopulations was done using Gene Ontology (GO) enrichment and gene set enrichment analysis. Results: SSc skin showed a decrease in number (P < 0.0001/P = 0.0004), area (P < 0.0001), and height (P < 0.0001) of papillae compared with controls and hypertrophic scars, respectively. The expression of papillary/reticular marker genes shifted toward a reticular expression profile in SSc. On the level of previously defined fibroblast populations, the increase of reticular marker genes was particularly pronounced in the PI16+ and SFRP4+ populations (P < 0.0001, respectively). Mechanistically, the expression of the WNT/β-catenin target AXIN2 and the number of fibroblasts with nuclear β-catenin-staining-pattern increased in the papillary compared with the reticular dermis in healthy skin. This polarization was lost in SSc with a two-fold increase in β-catenin-positive fibroblasts and AXIN2-expressing fibroblasts throughout the dermis (P = 0.0095). Enrichment of genes related to WNT/β-catenin-regulation was found in the PI16+ population that also relocates from the reticular to the papillary dermis in SSc. Conclusion: We demonstrate an association of the “reticularized” skin phenotype in SSc with a profound loss of physiologic spatial WNT/β-catenin-activation. Rescuing the spatial WNT/β-catenin-activation might help restore the physiologic skin organization in future therapeutic approaches of fibrosing disorders.
CRIS-Team Scopus Importer:2025-03-28

Do B-Cells play a Role in Patients with Psoriasis? - Banki, Simon; Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Documentation of psoriasis in routine care – expert consensus on a German data set - Otten, Marina; Mrowietz, Ulrich; Von Kiedrowski, Ralph Michael; Otto, Ramona; Altenburg, Andreas; Aschoff, Roland; Beissert, Stefan; Beiteke, Ulrike; Bonnekoh, Bernd; Hoffmann, Matthias; Koerber, Andreas; Maassen, Dirk; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background and objectives: Documenting patient data in psoriasis clinical practice can improve care, but standardized and transparent documentation is rare. The current project aimed to develop a data set for the documentation of psoriasis in daily practice. Material and methods: In four online Delphi rounds and one in-person meeting, 27 psoriasis experts allocated variables to a standard, an optimal and an optional data set. Most of the questions were standardized. Open questions were included to allow for the provision of reasons and to enlarge the data sets. Furthermore, in the in-person meeting we considered a) patients’ attitudes and b) dermatologists’ information on the current usage and acceptability in Germany. Results: The consensus approach resulted in a data set with 69 variables. The standard data set includes 20, the optimal data set 31 and the optional data set 18 variables. In summary, the data set can mainly be grouped into master data, general status and medical history data, medical history of psoriasis, status of psoriasis, diagnostics and comorbidity, therapies and patient-reported outcomes. Conclusions: The consensus recommendation of a standard, an optimal and an optional data set for routine care of psoriasis intends to be a decision-making aid and an orientation for both daily practice and further development of documentation systems.
CRIS-Team Scopus Importer:2021-10-22

Does Subjectively Perceived Loss Of Hand Function Sufficiently Represent Ultrasonography-Detected Synovitis And Tenosynovitis In Patients With Psoriasis And Psoriatic Arthritis? - Coppers, Birte; Bayat, Sara; Godonou, Elie-Tino; Valor-Mendez, Larissa; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Schett, Georg; Kleyer, Arnd; et al. (poster, European Alliance of Association for Rheumatology (EULAR) Congress, 2023)

Dokumentation der Psoriasis in der Routineversorgung – Expertenkonsens zu einem deutschen Datensatz - Otten, Marina; Mrowietz, Ulrich; von Kiedrowski, Ralph Michael; Otto, Ramona; Altenburg, Andreas; Aschoff, Roland; Beissert, Stefan; Beiteke, Ulrike; Bonnekoh, Bernd; Hoffmann, Matthias; Körber, Andreas; Maaßen, Dirk; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-10-29
Keywords: Datensatz; Delphi; Dokumentation; klinische Praxis; Patientenbeteiligung; Psoriasis

Doxycycline versus Prednisolone for the initial Treatment of bullous Pemphigoids: a pragmatic prospective randomized Study - Schmidt, E.; Benoit, S.; Ehrchen, J.; Glaeser, R.; Guenther, C.; Steinbrink, K.; Sticherling, Michael; Van Beek, N.; Wojnarowska, F.; Kirtschig, G.; Mason, J.; Godec, T.; et al. (2017)
EVALuna2:34351

Drei Generationen Leiden: Cryopyrin-assoziiertes periodisches Syndrom mit familiärer NLRP3-Mutation - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-02-04

Dupilumab but not cyclosporine treatment shifts the microbiome toward a healthy skin flora in patients with moderate-to-severe atopic dermatitis - Hartmann, Jan; Moitinho-Silva, Lucas; Sander, Nicole; Harder, Inken; Häsler, Robert; Rodriguez, Elke; Haufe, Eva; Kleinheinz, Andreas; Abraham, Susanne; Heratizadeh, Annice; Weisshaar, Elke; Schäkel, Knut; et al. (Allergy, 2023)
Background: Atopic dermatitis (AD) patients display an altered skin microbiome which may not only be an indicator but also a driver of inflammation. We aimed to investigate associations among AD patients' skin microbiome, clinical data, and response to systemic therapy in patients of the TREATgermany registry. Methods: Skin swabs of 157 patients were profiled with 16S rRNA gene amplicon sequencing before and after 3 months of treatment with dupilumab or cyclosporine. For comparison, 16s microbiome data from 258 population-based healthy controls were used. Disease severity was assessed using established instruments such as the Eczema Area and Severity Index (EASI). Results: We confirmed the previously shown correlation of Staphylococcus aureus abundance and bacterial alpha diversity with AD severity as measured by EASI. Therapy with Dupilumab shifted the bacterial community toward the pattern seen in healthy controls. The relative abundance of Staphylococci and in particular S. aureus significantly decreased on both lesional and non-lesional skin, whereas the abundance of Staphylococcus hominis increased. These changes were largely independent from the degree of clinical improvement and were not observed for cyclosporine. Conclusions: Systemic treatment with dupilumab but not cyclosporine tends to restore a healthy skin microbiome largely independent of the clinical response indicating potential effects of IL-4RA blockade on the microbiome.
CRIS-Team Scopus Importer:2023-05-05
Keywords: atopic dermatitis; dupilumab; inflammation; microbiome

Dupilumab-induced erythema nodosum in a patient with atopic hand eczema - Ronicke, Moritz; Sticherling, Michael; Wagner, Nicola (ALLERGOLOGIE, 2022)
CRIS-Team WoS Importer:2023-03-24

Effectiveness of an employee skin cancer screening program for secondary prevention - Uslu, Ugur; Hees, Felix; Winnik, Eva; Uter, Wolfgang; Sticherling, Michael (Cutis, 2016)
Incidences of UV-induced skin cancer are continuously increasing. For this reason, early diagnosis is becoming more important. In this study, 783 employees of a technical company participated in an employee skin cancer screening program, which consisted of a physical examination for benign and malignant skin lesions and premalignant conditions. To ensure the quality of the examinations, screening was only performed by 5 trained dermatologists. Participants also were asked to complete a standardized questionnaire prior to examination. A total of 661 skin lesions were diagnosed among 48% of participants; 12.8% of participants exhibited 50 or more melanocytic nevi and the risk for developing skin cancer was categorized as at least moderate for 64.9%. Additionally, 84.4% of participants with at least 1 skin lesion were advised to have a checkup within 1 year. The high rate of suspicious nevi detected in this study suggested that employee skin cancer screening programs are effective and also should be recommended at companies where employees are not at increased risk for developing skin cancer due to the nature of their work (eg, those who work outdoors). Despite the comparatively selective and young study population, these examinations provide evidence of the importance of skin cancer screening for the wider population.
EVALuna2:5563

Effectiveness of Tildrakizumab in the Long-Term Treatment of Plaque Psoriasis: A Retrospective, Multicenter Analysis Over 76 Weeks - Glatzel, Caroline; Fleißner, Janik; Shuti, Theodhora; Glatzel, Valerie; Dege, Tassilo; Schmieder, Astrid; Goebeler, Matthias; Sticherling, Michael; Kerstan, Andreas (Dermatologic Therapy, 2025)
Background: Psoriasis is a chronic inflammatory disease affecting skin and patients’ quality of life. Tildrakizumab is an IL-23p19-inhibitor approved for treatment of moderate-to-severe plaque psoriasis. Objective: To evaluate the effectiveness of tildrakizumab in daily practice in a heterogeneous cohort of patients with psoriasis often accompanied by comorbid (especially cardiometabolic) diseases. Methods: We conducted a retrospective analysis at two university outpatient clinics in Germany (April 2018 to June 2024), collecting data on patient characteristics, comorbidities, prior therapies, and treatment response. Results: The effectiveness analysis included 111 patients with psoriasis treated with tildrakizumab. Median PASI was 12.6 (IQR 11.0–18.6) at baseline and decreased to 6.0 (IQR 1.0–10.4) at Week 4, to 1.8 (IQR 1.0–10.4) at Week 16, and median PASI 0.00 (IQR 0.0–0.0) at Week 76. Median PASI < 3 was achieved by 64.6% at Week 16, 79.7% at Week 52 and 94.4% at Week 76 and PASI < 5 by 83.3% at Week 16, 94.2% at Week 52, and 100% at Week 76. The proportion achieving PASI75, PASI90, and PASI100 at Week 76 was 97.2%, 83.3%, and 58.3%. Patients with arterial hypertension (AHT) showed a lower PASI response compared to those without AHT, starting from Week 28 (p = 0.035) and continuing throughout the follow-up period. However, a detailed analysis indicates that patients with AHT also achieved PASI < 3 at Week 28 and beyond. Furthermore, patients with at least one cardiovascular risk factor (CRF: obesity, dyslipidemia, AHT, or type 2 diabetes mellitus, [46.8%]) demonstrated a less pronounced PASI response at Weeks 16, 28, and 64 compared to patients without such risk factors (pwk16 = 0.023; pwk28 = 0.012; pwk64 = 0.014). Median DLQI at baseline was 16.0 (IQR 9.5–22.0) and improved to 3.0 (IQR 1.0–8.0) at 4–16 weeks. Conclusion: This analysis confirmed effectiveness of tildrakizumab in a real-world setting, with notable improvements in PASI response observed in a heterogeneous patient cohort and a high level of quality of life improvement. It is noteworthy that patients with AHT and other CRF demonstrated lower treatment responses, indicating that these comorbidities may exert an influence on outcomes.
CRIS-Team Scopus Importer:2025-10-16
Keywords: biologicals; effectiveness; IL-23; psoriasis; real-world; tildrakizumab; treatment

Effectiveness, safety and drug survival of dupilumab in patients with moderate to severe atopic dermatitis: an interim analysis of the TREATgermany registry - Stoelzl, D.; Boraczynski, N.; Heratizadeh, A.; Haufe, Eva; Harder, I.; Abraham, S.; Heinrich, Luise; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Schaekel, K.; Ertner, K.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Effectiveness, safety and quality-of-life effects of guselkumab and ustekinumab in patients with psoriasis: Week 104 results from the non-interventional, prospective, German multicentre PERSIST study - Gerdes, S.; Hoffmann, M.; Asadullah, K.; Korge, B.; Mortazawi, D.; Krüger, N.; Personke, Y.; Tabori, S.; Gomez, M.; Wegner, S.; Kreimendahl, F.; Taut, F.; et al. (Journal of the European Academy of Dermatology and Venereology, 2023)
Background: PERSIST was a prospective, non-interventional, real-world study of guselkumab and ustekinumab in adult patients with moderate-to-severe plaque psoriasis in Germany. Objectives: To examine effectiveness, safety and quality-of-life (QoL) outcomes to Week (W) 104 of treatment with guselkumab and ustekinumab in patients with moderate-to-severe plaque psoriasis. Methods: Patients (≥18 years of age) received guselkumab or ustekinumab as per routine clinical practice. Outcomes to W104 were examined separately in guselkumab and ustekinumab recipients. An ad hoc exploratory analysis of outcomes with guselkumab versus ustekinumab was also performed following propensity score matching. Results: Overall, 302 and 313 patients received guselkumab and ustekinumab, respectively. Patients in both cohorts experienced improvements in disease activity and QoL that were maintained to W104, with 64.7% and 63.6% of guselkumab- and 54.6% and 64.4% of ustekinumab-treated patients achieving a Psoriasis Area and Severity Index (PASI) 90 response and a Dermatology Life Quality Index (DLQI) 0/1 score, respectively. Propensity score matching yielded well-balanced baseline characteristics except for prior biologic use, which was higher in guselkumab versus ustekinumab recipients (51.7% vs. 32.0%). Achievement of PASI ≤1 at W104 was more common in guselkumab versus ustekinumab recipients (58.7% vs. 49.7%). The W104 PASI90 response rate was 65.6% with guselkumab and 56.0% with ustekinumab; corresponding rates for PASI100 were 44.3% and 28.5%. In guselkumab recipients, response rates were higher in biologic-naïve versus biologic-experienced patients (PASI90, 77.1% vs. 53.4%; PASI100, 55.0% vs. 33.0%). A high level of response for QoL outcomes was observed for both treatments. Conclusions: Ustekinumab and guselkumab led to improvements in physician-assessed and patient-reported outcomes that were sustained for up to 2 years, with no new safety signals identified. Following propensity score matching, greater improvements in PASI outcomes were observed with guselkumab versus ustekinumab. Improvements with guselkumab were highest in biologic-naïve patients, highlighting the value of early treatment.
CRIS-Team Scopus Importer:2024-12-16

Effects of structured patient education in adults with atopic dermatitis: Multicenter randomized controlled trial - Heratizadeh, Annice; Werfel, Thomas; Wollenberg, Andreas; Abraham, Susanne; Plank-Habibi, Sibylle; Schnopp, Christina; Sticherling, Michael; Apfelbacher, Christian; Biedermann, Tilo; Breuer, Kristine; Fell, Isabel; Foelster-Holst, Regina; et al. (Journal of Allergy and Clinical Immunology, 2017)
BACKGROUND: Atopic dermatitis (AD) is a chronic relapsing skin disease prevalent in 1% to 3% of adults in Western industrialized countries. OBJECTIVE: We sought to investigate the effectiveness of educational training in an outpatient setting on coping with the disease, quality of life, symptoms, and severity in adults with AD. METHODS: In this German prospective, randomized controlled multicenter study, adult patients with moderate-to-severe AD were educated by referring to a comprehensive 12-hour training manual consented by a multiprofessional study group from different centers (Arbeitsgemeinschaft Neurodermitisschulung für Erwachsene [ARNE]). Patients were randomly allocated to the intervention or waiting control groups. Study visits were performed at baseline and after 1 year (1 year of follow-up). Primary outcomes were defined as a decrease in (1) "catastrophizing cognitions" with respect to itching (Juckreiz-Kognitions-Fragebogen questionnaire), (2) "social anxiety" (Marburger Hautfragebogen questionnaire), (3) subjective burden by symptoms of the disease (Skindex-29 questionnaire), and (4) improvement of disease signs and symptoms assessed by using the SCORAD index at 1 year of follow-up. Data were analyzed on an intention-to-treat basis. RESULTS: At 1 year of follow-up, patients from the intervention group (n = 168) showed a significantly better improvement compared with the waiting group (n = 147) in the following defined primary study outcomes: coping behavior with respect to itching (P < .001), quality of life assessed by using the Skindex-29 questionnaire (P < .001), and the SCORAD index (P < .001). CONCLUSIONS: This is the first randomized, controlled multicenter study on patient education in adult AD. The ARNE training program shows significant beneficial effects on a variety of psychosocial parameters, as well as AD severity.
EVALuna2:34346

European Dermatology Forum S1-guideline on the diagnosis and treatment of sclerosing diseases of the skin, Part 1: localized scleroderma, systemic sclerosis and overlap syndromes - Knobler, R.; Moinzadeh, P.; Hunzelmann, N.; Kreuter, A.; Cozzio, A.; Mouthon, L.; Cutolo, M.; Rongioletti, F.; Denton, C. P.; Rudnicka, L.; Frasin, L. A.; Smith, V.; et al. (Journal of the European Academy of Dermatology and Venereology, 2017)
The term 'sclerosing diseases of the skin' comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present guideline focuses on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, current strategies in the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 1 of this guideline provides clinicians with an overview of the diagnosis and treatment of localized scleroderma (morphea), and systemic sclerosis including overlap syndromes of systemic sclerosis with diseases of the rheumatological spectrum.
EVALuna2:34344

European dermatology forum S1-guideline on the diagnosis and treatment of sclerosing diseases of the skin, Part 2: Scleromyxedema, scleredema and nephrogenic systemic fibrosis - Knobler, R.; Moinzadeh, P.; Hunzelmann, N.; Kreuter, A.; Cozzio, A.; Mouthon, L.; Cutolo, M.; Rongioletti, F.; Denton, C. P.; Rudnicka, L.; Frasin, L. A.; Smith, V.; et al. (Journal of the European Academy of Dermatology and Venereology, 2017)
The term 'sclerosing diseases of the skin' comprises specific dermatological entities which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present guideline focuses on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, current strategies in the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 2 of this guideline provides clinicians with an overview of the diagnosis and treatment of scleromyxedema, scleredema (of Buschke) and nephrogenic systemic sclerosis (nephrogenic fibrosing dermopathy).
EVALuna2:34341

Extensive furuncular myiasis in a travel returnee from Africa - Rechtien, Laura; Kaufmann, Matthias; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2023)
CRIS-Team Scopus Importer:2023-02-17

Fatigue and Atopic Dermatitis: Results from the German Atopic Dermatitis Registery TREATgermany - Helmert, C.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder,; Kleinheinz, A.; Wollenberg, A.; Wiemers, F.; Weisshaar, E.; Augustin, M.; Von Kiedrowski, R.; Wildberg, J.; et al. (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

First real-world insights on benefit of apremilast treatment in patients with moderate to severe psoriasis after switching from fumaric acid esters from the APART Study - an interim analysis - Mrowietz, U.; Ertner, K.; Sticherling, Michael; Grosse, V.; Popp, G.; Roemmler-Zehrer, J.; Lampl, M.; Helget, U.; Gomez, Nunez N. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

From relative to absolute Treatment Goals - Correlation of PASI 90 and PASI <=2 in three clinical Studies with Secukinumab - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34398

From relative to absolute treatment outcomes-Correlation of PASI 90 and PASI <= 2 in three clinical trials with secukinumab - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34781

Fumaric Acid Esters and TNF alpha Inhibitors - Do they affect the Fertility of male Patients with Psoriasis? - Heppt, Franz; Colsmann, A.; Maronna, A.; Uslu, Ugur; Heppt, M.; Kiesewetter, Franklin; Sticherling, Michael (2017)
EVALuna2:34352

Fumaric Acid Esters: Patient Characteristics and Duration of Therapy from the PsoBest German Psoriasis Registry - Augustin, M.; Reich, K.; Spehr, C.; Rustenbach, S. J.; Mrowietz, U.; Radtke, M. A.; Wilsman-Theis, D.; Sticherling, Michael; Thaci, D. (2017)
EVALuna2:34356

Generalisierte pustulöse Psoriasis: Überblick zum Status quo und Ergebnisse einer Diskussionsrunde - Reich, Kristian; Augustin, Matthias; Gerdes, Sascha; Ghoreschi, Kamran; Kokolakis, Georgios; Mößner, Rotraut; Mrowietz, Ulrich; Navarini, Alexander A.; Pinter, Andreas; Schäkel, Knut; Staubach, Petra; Sticherling, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-06-24

Generalized pustular psoriasis: overview of the status quo and results of a panel discussion - Reich, Kristian; Augustin, Matthias; Gerdes, Sascha; Ghoreschi, Kamran; Kokolakis, Georgios; Mößner, Rotraut; Mrowietz, Ulrich; Navarini, Alexander A.; Pinter, Andreas; Schäkel, Knut; Staubach, Petra; Sticherling, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Generalized pustular psoriasis (GPP) is a rare, severe, potentially life-threatening, autoinflammatory, neutrophilic skin disease that may be accompanied by fever and leukocytosis. This paper describes the current state of knowledge on GPP in terms of classification, (differential) diagnosis and prevalence. We present a comparison of the genetics and pathoimmunology of GPP and psoriasis vulgaris with the central mechanisms of autoimmunology and autoinflammation. The currently available therapeutic options, expert recommendations for therapy, and data from early clinical trials investigating targeted therapies will be summarized. We present the results of our discussion with 13 experts for psoriasis vulgaris and GPP and give an integrated overview of indication and therapy based on our personal experience and present an outlook on further research questions. Collectively, this article highlights the high unmet need in GPP, as there exists no satisfactory method of diagnosis or treatment to date and new treatment options will be of great therapeutic benefit to those affected.
CRIS-Team Scopus Importer:2022-06-17

Genetic Analysis of MPO Variants in Four Psoriasis Subtypes in Patients from Germany - Haskamp, Stefan; Horowitz, Joseph; Oji, Vinzenz; Philipp, Sandra; Sticherling, Michael; Schäkel, Knut; Schuhmann, Sarah; Prinz, Jörg C.; Burkhardt, Harald; Behrens, Frank; Böhm, Beate; Köhm, Michaela; et al. (Journal of Investigative Dermatology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Guselkumab demonstrates long-term efficacy and maintenance of treatment response postwithdrawal in systemic treatment-naïve patients and nonresponders to fumaric acid esters: results from parts II and III of a randomized active-comparator-controlled phase IIIb trial (POLARIS). - Thaçi, Diamant; Pinter, Andreas; Sebastian, Michael; Termeer, Christian; Sticherling, Michael; Gerdes, Sascha; Schäkel, Knut; Wegner, Sven; Krampe, Stefanie; Bartz, Holger; Rausch, Christian; Taut, Friedemann; et al. (British Journal of Dermatology, 2024)
BACKGROUND: The anti-interleukin-23 antibody guselkumab (GUS) demonstrated favourable week 24 efficacy and safety over fumaric acid esters (FAE) in systemic treatment-naïve patients with moderate-to-severe plaque psoriasis (study part I). OBJECTIVES: To compare, in study part II, the sustainability of treatment responses (weeks 24-32) in GUS- and FAE-treated patients and treatment responses (weeks 32-56) in patients treated with GUS and FAE and in FAE nonresponders switching to GUS; and, in part III, to investigate the maintenance of response through week 100 in patients withdrawn from GUS at week 56. METHODS: At week 0, systemic treatment-naïve patients were randomized 1 : 1 to GUS or FAE as per label. At week 32, patients with a Psoriasis Area and Severity Index (PASI) 75 (≥ 75% improvement in PASI score) response (r) continued assigned treatment (GUSr-GUS; FAEr-FAE), whereas nonresponders (nr) received GUS (FAEnr-GUS; GUSnr-GUS). GUS-treated patients with a week 56 PASI 90 response (≥ 90% improvement in PASI score) were withdrawn (w) and followed until loss of response or week 100. RESULTS: At week 32, 98% (n = 54/55) of GUS- and 41% (n = 14/34) of FAE-treated patients were PASI 75 responders. At week 56, 91%, 50% and 80% of GUSr-GUS, FAEr-FAE and FAEnr-GUS patients, respectively, achieved a PASI 90 response; 72%, 29% and 45%, respectively, achieved a Dermatology Life Quality Index score of 0/1. At week 100, 44 weeks postwithdrawal, 47% (n = 17/36) and 25% (n = 3/12) of GUS-GUSw and FAE-GUSw patients, respectively, maintained a PASI score ≤ 5. Overall, the adverse event and discontinuation rates were lower for GUS than FAE. CONCLUSIONS: In these exploratory analyses, GUS, as a first-line systemic treatment or second-line systemic treatment in FAE nonresponders, was associated with long-term clinical efficacy up to week 100, including a withdrawal period.
EVALuna2:547035

Guselkumab is superior to fumaric acid esters in patients with moderate-to-severe plaque psoriasis who are naive to systemic treatment: results from a randomized, active-comparator-controlled phase IIIb trial (POLARIS) - Thaci, D.; Pinter, A.; Sebastian, M.; Termeer, C.; Sticherling, Michael; Gerdes, S.; Wegner, S.; Krampe, S.; Bartz, H.; Rausch, C.; Mensch, A.; Eyerich, K. (British Journal of Dermatology, 2020)
Background Guselkumab, a fully human interleukin-23 antibody, is approved for systemic treatment of patients with moderate-to-severe plaque psoriasis. Objectives To compare the efficacy and safety of guselkumab with those of fumaric acid esters (FAE) in patients with moderate-to-severe plaque psoriasis who are naive to systemic treatment. Methods Eligible patients were randomized to this multicentre, randomized, open-label, assessor-blinded, active-comparator-controlled phase IIIb study to receive guselkumab 100 mg by subcutaneous injection or oral FAE according to local label guidelines. Results Through week 24, 56 of 60 patients completed guselkumab treatment and 36 of 59 completed FAE treatment. The primary endpoint (proportion of patients with >= 90% improvement from their baseline Psoriasis Area and Severity Index; PASI 90 response) was achieved by significantly more patients receiving guselkumab than FAE at week 24 (82% vs. 14%, P < 0 center dot 001). Analysis of the major secondary endpoints confirmed a statistically significant difference between the treatments with regards to PASI 75 response (90% vs. 27%, P < 0 center dot 001) and Dermatology Life Quality Index score of 0 or 1 (no effect at all on the patient's quality of life; 62% vs. 17%, P < 0 center dot 001). More patients in the guselkumab group achieved completely clear skin (PASI 100 response) than in the FAE group (32% vs. 3%, P < 0 center dot 001). The incidence of adverse events was lower with guselkumab than with FAE (73% vs. 98%). Overall, 28% of patients on FAE discontinued due to an adverse event, compared with none receiving guselkumab. No new safety findings were observed for guselkumab. Conclusions Guselkumab demonstrated superiority over FAE in systemic-treatment-naive patients with moderate-to-severe plaque psoriasis through 24 weeks. What's already known about this topic?
CRIS-Team WoS Importer:2020-01-28

HAND FUNCTION IS IMPAIRED IN PATIENTS WITH RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS, AND PSORIASIS COMPARED TO HEALTHY CONTROLS - Liphardt, Anna-Maria; Liehr, Sonja; Manger, Eva; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

H. E. Becher - his Importance as a Sculptor and Medalist for Moulage Art in Germany - Sticherling, Michael; Emmerling, Johanna (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Hydradenitis suppurativa - new exploration on the famous Disease - Oetterich, Kerstin; Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34354

Identification of circulating microRNA patterns in patients in psoriasis and psoriatic arthritis - Haschka, Judith; Simon, David; Bayat, Sara; Messner, Zora; Kampylafka, Eleni; Fagni, Filippo; Skalicky, Susanna; Hackl, Matthias; Resch, Heinrich; Zwerina, Jochen; Kleyer, Arnd; Cavallaro, Alexander Josef; et al. (Rheumatology, 2023)
Objective miRNAs are small non-coding RNAs that control gene expression. Specific intra- and extracellular miRNA signatures have been identified in various diseases. Whether certain miRNA signatures are associated with psoriasis (PsO) and PsA is currently unknown. We aimed to search for circulating miRNA signatures associated with PsO and PsA patients. Methods Expression of miRNAs was analysed by reverse transcription quantitative real-time PCR (RT-qPCR) in the serum of PsA, PsO patients and healthy controls. Demographic and disease-specific characteristics and imaging data from hand MRI were recorded. In the discovery phase, 192 miRNA assays were analysed in 48 samples (PsA, PsO, controls: each N = 16). For validation, 17 selected miRNAs were measured in the total population. Results A total of 141 patients and controls were analysed (51 PsA, 40 PsO, 50 controls). In the discovery phase 51 miRNAs in PsO and 64 miRNAs in PsA were down- or upregulated compared with controls, with 33 miRNAs being changed in both (adj. P < 0.05). The 17 top candidates from discovery were assessed in the validation phase, 9 of them discriminated PsA and PsO from controls [area under the curve (AUC) >= 0.70, all P < 0.05]. Four miRNAs (miR-19b-3p, miR-21-5p, miR-92a-3p and let-7b-5p) were significantly differently regulated between PsO and PsA. A combination of these miRNAs increased the AUC to 0.92 in multivariate regression model to discriminate PsO and PsA. Conclusion miRNA signatures in PsA and PsO patients differ from controls. Nine miRNAs were differentially regulated in PsA and PsO patients, five of them previously reported to be involved in bone and cartilage metabolism, indicating an intimate association of psoriatic inflammation and bone/cartilage changes.
CRIS-Team WoS Importer:2023-03-17

IDENTIFICATION OF CIRCULATING MICRORNA SIGNATURES IN PATIENTS WITH PSORIASIS WITH SUBCLINICAL JOINT DISEASE AND PATIENTS WITH PSORIATIC ARTHRITIS - Haschka, J.; Simon, David; Bayat, Sara; Messner, Z.; Kampylafka, E.; Fagni, Filippo; Skalicky, S.; Hackl, M.; Resch, H.; Zwerina, J.; Kleyer, Arnd; Sticherling, Michael; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Identification of two novel bullous pemphigoid- associated alleles, HLA-DQA1*05:05 and -DRB1*07:01, in Germans - Schwarm, Christian; Gola, Damian; Holtsche, Maike M.; Dieterich, Anabelle; Bhandari, Anita; Freitag, Miriam; Nürnberg, Peter; Toliat, Mohammad; Lieb, Wolfgang; Wittig, Michael; Franke, André; Worm, Margitta; et al. (Orphanet Journal of Rare Diseases, 2021)
Bullous pemphigoid (BP) is the most common autoimmune skin blistering disease characterized by autoimmunity against the hemidesmosomal proteins BP180, type XVII collagen, and BP230. To elucidate the genetic basis of susceptibility to BP, we performed the first genome-wide association study (GWAS) in Germans. This GWAS was combined with HLA locus targeted sequencing in an additional independent BP cohort. The strongest association with BP in Germans tested in this study was observed in the two HLA loci, HLA-DQA1*05:05 and HLA-DRB1*07:01. Further studies with increased sample sizes and complex studies integrating multiple pathogenic drivers will be conducted.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Autoimmune blistering skin diseases; Bullous pemphigoid; Germans; GWAS; HLA

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

Impairment of gustatory and olfactory senses in plaque psoriasis - Rueter, P.; Gruenthaler, V.; Zopf, Yurdagül; Sticherling, Michael (2017)
EVALuna2:34082

Impairment of Taste and Smell in Psoriasis- another Cause of Impaired Calorie Intake? - Gruenthaler, V.; Rueter, P.; Zopf, Yurdagül; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Impfungen in aller Munde – Relevanz auch für die Dermatologie? - Sticherling, Michael (Hautarzt, 2021)
CRIS-Team Scopus Importer:2021-02-05

Impfungen in der Dermatologie - Sticherling, Michael (Hautarzt, 2021)
Vaccinations are among the most successful prophylactic measures in medicine. As they are applied to healthy subjects, regulatory steps before licensing of any vaccination are strictly based on clinically controlled studies as well as on registry data in the further course. The probability and relevance of adverse reactions to vaccinations have to be weighed against any harm through the respective natural infection as well as the vaccination-induced protection against infections. Intolerance reactions to vaccinations are far more suspected than proven and altogether rare. Among these, specific dermatoses like psoriasis, atopic dermatitis and lichen planus are found as well as allergic reactions and a number of more nonspecific skin symptoms. Apart from provocation or exacerbation of an underlying dermatological disease, various intolerance reactions may be encountered which are classically allergologic or anaphylactoid. People with chronic dermatoses, especially those on immunosuppressive and immunomodulatory therapy, should have all recommended standard vaccinations. Vaccinations should not be administered during acute skin manifestations and relevant comedication—especially if immunomodulatory or immunosuppressive—has be taken into account in the decision to vaccinate and to define the time point of any vaccination. Inactivated vaccines may be administered even during ongoing immunosuppressive therapy, but may result in decreased immunological reactions and protection to infection. Live vaccines should be avoided.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Adverse reactions; Atopic dermatitis; Intolerance reactions; Lichen planus; Psoriasis

Implementation of dupilumab in routine care of atopic eczema. Results from the German national registry TREATgermany - Abraham, Susanne; Haufe, Eva; Harder, Inken; Heratizadeh, Annice; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Augustin, Matthias; Wiemers, Franca; Zink, Alexander; Biedermann, Tilo; Von Kiedrowski, Ralph; et al. (British Journal of Dermatology, 2020)
The German atopic eczema (AE)-registry TREATgermany is a non-interventional multicenter patient cohort study for adult patients with currently moderate-to-severe disease activity or current/previous anti-inflammatory systemic treatment.1,2 Dupilumab has demonstrated to be an effective treatment for patients with moderate-to-severe AE in clinical trials.3-5 Real world evidence is now needed to evaluate its effectiveness and safety in routine care.
EVALuna2:212857

Infektiöse Reisedermatosen - Rongisch, Robert; Schmidt, Enno; Deresz, Nicolai; Deresz, Katharina; Schöfer, Helmut; Schäkel, Knut; Jakob, Thilo; Maurer, Marcus; Sticherling, Michael; Sunderkötter, Cord; Babilas, Philipp; Spornraft-Ragaller, Petra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-07-31

Inflammatory Skin Diseases: The Importance of Immunological Signatures - Garzorz-Stark, Natalie; Weidinger, Stephan; Sticherling, Michael; Ghoreschi, Kamran; Enk, Alexander; Eyerich, Kilian (Deutsches Ärzteblatt international, 2025)
Background: The understanding and classification of inflammatory skin diseases is shifting from a historical-descriptive perspective to a molecular-pathophysiological one based on immune response patterns. These are derived from a few key immunological mediators, each of which induces its own characteristic clinical, histopathological, and molecular patterns in the skin. Methods: This discussion of the definition of the immune response patterns of inflammatory skin diseases is based on information from pertinent publications retrieved by a selective literature search. A systematic literature search was also conducted on the response of inflammatory skin diseases to treatment with specific biologic agents. Results: The described immune response patterns are: autoinflammation; type 1, cytotoxic; type 2a, eczematous; type 2b, blistering; type 3, psoriasiform; type 4a, fibrosing; and type 4b, granulomatous. Each signature can usually be treated in a targeted manner. In general, each therapeutic target structure is associated with an adequate treatment response if and only if the skin disease under treatment has the relevant signature type. Hardly any biomarkers are currently available for the determination of immune response patterns in routine clinical practice. Conclusion: The classification of inflammatory skin diseases by their immune response patterns opens up the prospect of specifically targeted immunotherapy for each immune response pattern regardless of the historical-descriptive disease entity. Targeting is intended to improve response rates. Initial findings suggest that this strategy is likely to succeed.
CRIS-Team Scopus Importer:2025-07-10

Influence of TNF-alpha inhibitors and fumaric acid esters on male fertility in psoriasis patients - Heppt, Franz; Colsman, A.; Maronna, A.; Uslu, Ugur; Heppt, M. V.; Kiesewetter, Franklin; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: Is there any influence of a therapy with TNF-alpha inhibitors or fumaric acid esters and of disease activity status on male fertility and sperm quality in patients with psoriasis? METHODS: In this monocentric, open-label, prospective study, semen samples were collected from patients receiving either TNF-alpha inhibitors or fumaric acid esters for moderate-to-severe plaque psoriasis. Semen was analysed at baseline before onset of the systemic therapy and monitored every 3 months under therapy. Sperm parameters were assessed according to the current WHO definitions. RESULTS: In total, 101 semen specimens from 27 patients were obtained. Mean Psoriasis Area and Severity Index (PASI) score at baseline was 11.05. Only 14.8% of patients showed a normozoospermia without any other abnormal seminal values. 85.2% of patients had at least one sperm/seminal abnormality, including two patients showing an azoospermia. Interestingly, 48.1% showed sperm parameters indicative of genital tract inflammation. Therapy with TNF-alpha inhibitors or fumaric acid esters did not have any negative effects on relevant sperm parameters such as mean total sperm number, sperm concentration, total and progressive motility. No major gonadal dysfunction was observed in any patient. CONCLUSION: At baseline, many patients with psoriasis showed abnormal semen/sperm parameters and remarkably elevated leukocytes and values of seminal polymorphonuclear elastase, indicating a genital tract inflammation. Thus, genital tract inflammation may represent an important comorbidity of psoriasis, little attention paid to so far. Regarding treatment with TNF-alpha inhibitors or fumaric acid esters, no major negative (side-) effects on sperm quality were observed.
EVALuna2:34337

Insights From the Apremilast After Switching From Fumaric Acid Ester Treatment (APART) Study: An Interim Real-World Safety Analysis - Mrowietz, Ulrich; Ertner, Konstantin; Sticherling, Michael; Grosse, Virginia; Popp, Georg; Schwichtenberg, Uwe; Karl, Lars; Schenck, Florian; Ramaker-Brunke, Jutta; Roemmler-Zehrer, Josefine; Helget, Ursula; Gomez, Natalie Nunez (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-02-28

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Interleukin 17 Blockade in Psoriasis Patients with Subclinical Joint Inflammation- Prospective Open Study to Influence the Course of the Disease by means of Secukinumab - Kampylafka, E.; Oliveira, I.; Linz, C.; Lerchen, V.; Englbrecht, Matthias; Simon, David; Rech, Jürgen; Kleyer, Arnd; Schett, Georg; Sticherling, Michael; Hueber, Axel (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Interleukin-17 Blockade Leads to Shifts from Stage-based Towards Response-based Disease Clusters- Comparative Data from Very Early and Established Psoriatic Arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Investigation of the expression of inflammatory markers in oral biofilm samples in patients with systemic scleroderma and the association with clinical periodontal parameters— a preliminary study - Buchbender, Mayte; Lugenbühl, Amelie; Fehlhofer, Jakob Paul; Kirschneck, Christian; Ries, Jutta; Lutz, Rainer; Sticherling, Michael; Kesting, Marco Rainer; Ries, Jutta (Life, 2021)
Background: Systemic scleroderma (SSc) has multiple orofacial effects. The aim of this study was to analyze the expression of inflammatory mediators in biofilm samples. It was hypothesized that different expression levels and clinical associations might be drawn. Methods: A total of 39 biofilm samples from group 1 = SSc and group 2 = healthy control were examined for the expression levels of interleukin (IL)-2,-6, and-10; matrix metalloprotease (MMP)-9; and surface antigens CD90 and CD34 by quantitative real-time PCR and clinical parameters. Relative quantitative (RQ) gene expression was determined using the ∆∆CT method. Results: The mean bleeding on probing values (p = 0.006), clinical attachment loss (CAL) (p = 0.009), gingival recession (p = 0.020), limited mouth opening (p = 0.001) and cervical tooth defects (p = 0.011) were significantly higher in group 1. RQ expressions of IL-2 and CD34 were significantly lower, IL-6, MMP-9, and CD90 were significantly higher. There was a significant positive correlation of IL-6/MMP-9 and negative correlation of mouth opening/CAL and IL-6/CAL. Conclusion: Different expression levels of IL-2, IL-6, MMP-9, CD34 and CD90 were detected in biofilm samples from patients with SSc compared to control. An immunological correlation to the clinical parameters of mouth opening and CAL was shown; thus, we conclude that SSc might have an impact on periodontal tissues.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Biofilm samples; Expression levels of cytokines; Periodontal parameters; Systemic sclero-derma (SSc)

Itching and Neurodermatitis: Results from the German Neurodermatitis Register TREATgermany - Haufe, Eva; Heinrich, Luise; Weisshaar, Elke; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Wiemers, Franca; Augustin, Matthias; Zink, Alexander; Von Kiedrowski, Ralph; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-02-28

Itching and treatments in atopic dermatitis (AD): results from the German AD registry TREATgermany - Weisshaar, Elke; Bentz, Philipp; Haufe, Eva; Heinrich, Luise; Apfelbacher, Christian; Heratizadeh, Annice; Abraham, Susanne; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Schäkel, Knut; Wiemers, Franca; et al. (British Journal of Dermatology, 2023)
CRIS-Team Scopus Importer:2023-05-05

Itching in Atopic Dermatitis: Patient-and Physician-reported Outcomes in the German Atopic Dermatitis Registry TREATgermany - Weisshaar, Elke; Bentz, Philipp; Apfelbacher, Christian; Haufe, Eva; Heinrich, Luise; Heratizadeh, Annice; Abraham, Susanne; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Schäkel, Knut; Wiemers, Franca; et al. (Acta Dermato-Venereologica, 2023)
TREATgermany is an investigator-initiated prospective disease registry. It investigates physician-and patient-reported disease severity (Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), Investigator Global Assessment, Patient-Oriented Eczema Measure (POEM), Patient Global Assessment (PGA)), patient-reported symptoms (itch, sleep loss, depressive symptoms), therapy courses and dermatological quality of life (DLQI) in moderate-to-severe atopic dermatitis with SCORAD > 20. 1,134 atopic dermatitis patients (mean age 41.0 ± 14.7 years, 42.5% females) were enrolled by 40 German recruiting sites (dermatological clinics and practices) between June 2016 and April 2021. The cur-rent analysis focuses on itch scores obtained with a numerical rating scale (NRS)) documented for the pre-vious 3 days prior to baseline visit. The results show that 97.2% (1,090 of 1,121) patients experienced itch. Itch severity correlated moderately with severity of atopic dermatitis oSCORAD (rho = 0.44 (0.39–0.48)) and EASI score (rho = 0.41 (0.36–0.46)). A strong cor-relation was found with self-reported disease severity as PGA (rho = 0.68 (0.65–0.71)), POEM sum score (rho = 0.66 (0.63–0.69)) and dermatological quality of life impairment DLQI (rho = 0.61 (0.57–0.65)). Itch as a subjective complaint is more closely correlated with patient-reported outcomes than with objective assessments by the physician.
CRIS-Team Scopus Importer:2023-02-10
Keywords: EASI; POEM; pruritus; quality of life; registry

Itch, sleep loss, depressive symptoms, fatigue, and productivity loss in patients with moderate-to-severe atopic dermatitis: Analyses of TREATgermany registry data - Birkner, Thomas; Siegels, Doreen; Heinrich, Luise; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Bell, Magnus; Fell, Isabell; Worm, Margitta; Handrick, Christiane; Effendy, Isaak; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Background: TREATgermany is a multicenter registry including patients with moderate-to-severe atopic dermatitis (AD) from currently 74 study centers (university clinics, hospitals and practices) in Germany. As of August 31, 2021, 1,230 adult patients were enrolled. Methods: In TREATgermany, patients and physicians fill in questionnaires pertaining to symptoms, disease severity, quality of life, depressiveness, and fatigue. In particular, limitations in work performance are assessed using the Work Limitations Questionnaire (WLQ). To assess associations between occupational performance/work limitations and symptoms, correlations and regression models were calculated. Results: The examined sample of 228 employed patients reported an average of 6% at-work productivity loss within the past two weeks prior to enrolment in the registry. The WLQ productivity loss score was moderately associated with itch (r = 0.32) and sleep loss (r = 0.39) and strongly associated with depressive symptoms (r = 0.68) and fatigue (r = 0.60). Conclusions: The analyses of the registry data show that moderate-to-severe atopic dermatitis has a negative impact on the work productivity of the patients. The analyses further point out the relevant associations between work productivity, depressive symptoms, and fatigue highlighting the disease burden caused by the psychological components of AD.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Atopic dermatitis; productivity loss; registry; work limitations

Juckreiz, Schlafstörungen, depressive Symptome, Fatigue und Einschränkungen der Arbeitsproduktivität bei Patienten mit moderater bis schwerer atopischer Dermatitis: Daten aus dem TREATgermany-Register - Birkner, Thomas; Siegels, Doreen; Heinrich, Luise; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Bell, Magnus; Fell, Isabell; Worm, Margitta; Handrick, Christiane; Effendy, Isaak; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-11-10
Keywords: Arbeitseinschränkungen; Atopic dermatitis; Atopische Dermatitis; productivity loss; Produktivitätsverlust; Register; registry; work limitations

Localized Scleroderma of the Head and Face Area: A Retrospective Cross-sectional Study of 96 Patients from 5 German Tertiary Referral Centres - Kreuter, Alexander; Mitrakos, Georg; Hofmann, Silke C.; Lehmann, Percy; Sticherling, Michael; Krieg, Thomas; Lahner, Nina; Tigges, Christian; Hunzelmann, Nicolas; Moinzadeh, Pia (Acta Dermato-Venereologica, 2018)
EVALuna2:34377

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Lungs Ailment - other Comorbidity of the Psoriasis? - Moreira, Alvaro; Sticherling, Michael (2017)
EVALuna2:34355

Lupus erythematosus - Sticherling, Michael; Kuhn, Annegret (Springer Berlin Heidelberg, 2022)
Lupus erythematosus (LE) is an inflammatory autoimmune disease characterized by high clinical heterogeneity and a variable course. In systemic lupus erythematosus (SLE), there is the possibility of the development of life-threatening involvement of multiple organs that can affect the skin, musculosceletal system, kidneys, and cardiovascular and central nervous systems. The disease can also be limited to the skin, and is then called cutaneous lupus erythematosus (CLE). Together with an (immune) genetic background, various environmental factors, such as smoking, medication, hormones, infections, and above all ultraviolet (UV) radiation can lead to an initial manifestation or exacerbation of the disease. New findings on the pathogenesis of CLE have also led to further therapeutic options for this autoimmune disease.
CRIS-Team Scopus Importer:2024-12-16

MAGNETIC RESONANCE IMAGING (MRI) OF HANDS OF PSORIASIS PATIENTS: HIGH INCIDENCE OF INFLAMMATION - Simon, David; Faustini, F.; Englbrechtl, M.; Kleyer, Arnd; Kocijan, R.; Haschka, J.; Kraus, S.; Hueber, Axel; Sticherling, Michael; Schell, G.; Rech, Jürgen (2014)
EVALuna2:12862

Meeting Report of the Pathogenesis of Pemphigus and Pemphigoid Meeting in Munich, September 2016 - Schmidt, Enno; Spindler, Volker; Eming, Ruediger; Amagai, Masayuki; Antonicelli, Frank; Baines, John F.; Belheouane, Meriem; Bernard, Philippe; Borradori, Luca; Caproni, Marzia; Di Zenzo, Giovanni; Grando, Sergei; et al. (Journal of Investigative Dermatology, 2017)
Autoimmune blistering diseases are a heterogeneous group of about a dozen complex disorders that are characterized by intraepidermal (pemphigus) and subepidermal blistering (pemphigoid diseases and dermatitis herpetiformis). The Pathogenesis of Pemphigus and Pemphigoid Meeting, organized by the Departments of Dermatology in Lübeck and Marburg and the Institute of Anatomy and Cell Biology, Munich, was held in September 2016 in Munich. The meeting brought together basic scientists and clinicians from all continents dedicating their work to autoimmune blistering diseases. Considerable advances have been made in describing incidences and prevalences of these diseases and linking comorbidities with autoantibody reactivities and clinical variants, for example, dipeptidyl peptidase-IV inhibitor-associated noninflammatory bullous pemphigoid. Although new entities are still being described, diagnosis of most autoimmune blistering diseases can now be achieved using standardized and widely available serological test systems. Various experimental mouse models of pemphigus and pemphigoid disease are increasingly being used to understand mechanisms of central and peripheral tolerance and to evaluate more specific treatment approaches for these disorders, such as molecules that target autoreactive T and B cells and anti-inflammatory mediators, that is, dimethyl fumarate, phosphodiesterase 4, and leukotriene B4 inhibitors in pemphigoid disorders, and chimeric antigen receptor T cells in pemphigus. Very recent experimental data about the immunopathology and the determinants of autoantibody formation and keratinocyte susceptibility in pemphigus were discussed. With regard to cellular mechanisms leading to the loss of cell-cell adhesion, new ideas were shared in the field of signal transduction. Major steps were taken to put the various partly contradictory and controversial findings about the effects of pemphigus autoantibodies and other inflammatory mediators into perspective and broaden our view of the complex pathophysiology of this disease. Finally, two investigator-initiated multicenter trials highlighted doxycycline and dapsone as valuable medications in the treatment of bullous pemphigoid.
EVALuna2:34348

Multiple Dermal Abscesses by Trichophyton rubrum in an Immunocompromised Patient - Toussaint, Frédéric; Sticherling, Michael (Frontiers in Medicine, 2019)
We report the case of a 52-year-old man who presented with a 10 year history of multiple nodules with purulent drainage on the upper extremities. Several attempts of treatment with oral antibiotics had been unsuccessful. A skin biopsy specimen showed a dermal abscess with branched septate hyphae. A mycological culture of pus and of the biopsy specimen revealed Trichophyton rubrum. Deeper dermatophytosis presenting as dermal abscesses is a rare disease which occurs normally in immunocompromised conditions. Our patient was on immunosuppressive therapy with methylprednisolone and azathioprine because of inflammatory demyelinating polyneuropathy and presented with extensive abscesses. In cases of dermal abscesses it is important to not only consider bacterial but also fungal infections as underlying cause.
CRIS-Team WoS Importer:2019-05-24

Multiple dermal Abscesses by Trichophyton rubrum in an immunosuppressed Patients - Toussaint, Frédéric; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Multiple thoracic Erosions after Vacation in Tunisia - Meder, Christine; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Mutations in IL36RN in patients with generalized pustular psoriasis - Koerber, Andreas; Moessner, Rotraut; Renner, Regina; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Schulz, Peter; Sticherling, Michael; Traupe, Heiko; Hüffmeier, Ulrike (Journal of Investigative Dermatology, 2013)
EVALuna2:9180

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Neural Networks for Distinguishing Rheumatoid Arthritis from Psoriatic Arthritis by Using Magnetic Resonance Imaging - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Arthritis Rheumatol., 2022)

Noonan Syndrome with multiple Lentigines (Leopard Syndrome) - Case Description of a 45-year-old Patient - Sponagl, F.; Sticherling, Michael; Seybold, H.; Erdmann, M.; Wagner, N. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Obesity is linked to disease severity in moderate to severe atopic dermatitis—Data from the prospective observational TREATgermany registry - Traidl, Stephan; Hollstein, Moritz M.; Kroeger, Nadine; Fischer, Sascha; Heratizadeh, Annice; Heinrich, Luise; Kind, Barbara; Siegels, Doreen; Abraham, Susanne; Schäfer, Thomas; Augustin, Matthias; Harder, Inken; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
Background: There are conflicting data on a potential association between obesity and atopic dermatitis (AD). The purpose of this study was to investigate the relationship between obesity and AD disease severity. Methods: Patients from the TREATgermany registry cohort were divided into three groups according to their body mass index (BMI). Due to low numbers, underweight patients (BMI <18.5 kg/m2) were excluded from the analysis. Physician- and patient-reported disease severity scores as well as additional phenotypic characteristics were evaluated for association with BMI. Generalized linear mixed models and multinomial logit models, respectively, were applied to investigate the association of BMI, age, sex and current systemic AD treatment with disease severity. Results: This study encompassed 1416 patients, of which 234 (16.5%) were obese (BMI ≥30 kg/m2). Obesity was associated with lower educational background and smoking. Otherwise, obese and non-obese AD patients had similar baseline characteristics. Increased BMI was associated with higher oSCORAD (adjusted β: 1.24, 95% CI: 1.05–1.46, p = 0.013) and Patient-oriented eczema measure (POEM) (adjusted β: 1.09, 95% CI: 1.01–1.17, p = 0.038). However, the absolute difference in the overall oSCORAD was small between obese and non-obese AD patients (Δ oSCORAD = 2.5). Allergic comorbidity was comparable between all three groups, with the exception of asthma which was more pronounced in obese patients (p < 0.001). Discussion: In this large and well-characterized AD patient cohort, obesity is significantly associated with physician- and patient-assessed measures of AD disease severity. However, the corresponding effect sizes were low and of questionable clinical relevance. The overall prevalence of obesity among the German AD patients was lower than in studies on other AD cohorts from different countries, which confirms previous research on the German population and suggests regional differences in the interdependence of AD and obesity prevalence.
CRIS-Team Scopus Importer:2024-05-03

Objective and subjective hand function reflect grade of tenosynovitis in patients with psoriasis and psoriatic arthritis - Coppers, Birte; Bayat, Sara; Godonou, Elie-Tino; Valor-Mendez, Larissa; Simon, David; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Bohr, Daniela; Schönau, Verena; Sticherling, Michael; Schett, Georg; et al. (poster, Deutsche Gesellschaft für Rheumatologie Kongress, 2023)

Palmoplantar Pustular Psoriasis Is Associated with Missense Variants in CARD14, but Not with Loss-of-Function Mutations in IL36RN in European Patients - Moessner, Rotraut; Frambach, Yvonne; Wilsmann-Theis, Dagmar; Loehr, Sabine; Jacobi, Arnd; Weyergraf, Ansgar; Mueller, Michael; Philipp, Sandra; Renner, Regina; Traupe, Heiko; Burkhardt, Harald; Kingo, Kuelli; et al. (Journal of Investigative Dermatology, 2015)
EVALuna2:9269

PASI <= 2 corresponds to PASI 90, irrespective of baseline severity: A post-hoc analysis of the PRIME-study - Reich, K.; Sieder, C.; Bachhuber, T.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34343

Patient Characteristics and Treatment Patterns in European Pediatric Patients with Psoriasis: A Real-World, Cross-Sectional Study - Sticherling, Michael; Mcpherson, Tess; Laguna, Raul De Lucas; Costanzo, Antonio; Reed, Catherine; Artime, Esther; Robert, Camille; Lucas, James; Schuster, Christopher; Mahe, Emmanuel (Dermatology and Therapy, 2022)
Introduction This study evaluated patient characteristics and treatment patterns according to weight in pediatric patients with psoriasis in a real-world setting. Methods Primary care and specialist physicians treating pediatric patients with psoriasis aged 6-17 years in five European countries were surveyed in the 2019-2020 Adelphi Real World Pediatric Psoriasis Disease Specific Programme. At least two patients with current or previous biologic use were included per physician. Patient characteristics and treatment patterns were analyzed overall and for patients weighing 25-50 kg or more than 50 kg. Results Data from 772 patients weighing 25-50 kg and 1147 weighing more than 50 kg were analyzed. Median age at diagnosis was significantly less in lighter than heavier patients (10.0 vs. 14.0 years; p < 0.001), as was median disease duration (2.2 vs. 3.0 years; p < 0.001). Topical treatments were prescribed in 59.0% of patients overall (70.3% of lighter and 51.4% of heavier patients; p < 0.001), and were used to treat mild rather than moderate-to-severe psoriasis. Conventional systemic use was low (10.8% of patients overall) and predominantly for moderate-to-severe psoriasis. In this biologic-enriched sample, most biologics (78.2%) were prescribed in older (> 13 years) patients. Biologic use increased with line of therapy (6.6% of first-line, 18.0% of second-line, 33.7% of third-line, 44.7% of fourth-line treatments). Conclusion Biologics are predominantly prescribed in older (> 13 years) and heavier (> 50 kg) patients, with little first- or second-line use. The low use of biologics in European pediatric patients with psoriasis may represent an unmet treatment need, as topical or conventional systemic agents remain the main treatment option for moderate or severe psoriasis in these patients through the treatment pathway.
CRIS-Team WoS Importer:2022-07-22

Patient-reported Outcomes and Burden of Disease in Paediatric Patients with Psoriasis: Real-world Data from EU5 and US - Seyger, Marieke M.B.; Paller, Amy; Sticherling, Michael; Bachhuber, Teresa; Thomas, Nicolas; Hetherington, James; Lucas, James; Richardson, Craig; Augustin, Matthias (Acta Dermato-Venereologica, 2023)
CRIS-Team Scopus Importer:2023-04-28

Patient-reported outcomes and burden of disease in paediatric patients with psoriasis: real-world data from the EU5 and USA - Seyger, M.; Paller, A.; Sticherling, Michael; Bachhuber, T.; Fang, J.; Hetherington, J.; Lucas, J.; Meakin, S.; Richardson, C.; Augustin, M. (BRITISH JOURNAL OF DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-01-14

Patients' and Physicians' Preferences for Systemic Psoriasis Treatments: A Nationwide Comparative Discrete Choice Experiment (PsoCompare) - Schaarschmidt, Marthe-Lisa; Herr, Raphael M.; Gutknecht, Mandy; Wroblewska, Katharina; Gerdes, Sascha; Sticherling, Michael; Augustin, Matthias; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2018)
Systemic antipsoriatic treatment options are increasing rapidly. The aim of this nationwide discrete choice experiment was to compare patients' (n = 222) and physicians' (n = 78) preferences for outcome and process attributes of systemic antipsoriatics using Relative Importance Scores (RIS). Both groups considered Psoriasis Area and Severity Index 90 (PASI 90) to be most important (RIS 21.4 and 20.8, respectively). Moreover, patients were highly concerned about mild and severe adverse events (RIS = 18.2 and 14.2), physicians about severe adverse events (RIS = 14.9) and cost (RIS = 13.8). Compared to physicians, patients worried more about mild adverse events and treatment location, but less about cost and frequency of laboratory tests. Physicians' preferences were influenced by work experience and percentage of biological prescriptions, patients' preferences by age, disease duration and severity. Older and less severely affected patients recruited via a patient organization focused more on safety, but less on efficacy and time until response than did patients from study centres. In conclusion, these differences in trade-offs should be integrated into a shared decision-making.
EVALuna2:34404

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

PATIENTS WITH IMMUNE MEDIATED INFLAMMATORY DISEASES ARE OVERREPRESENTED IN LOW-FREQUENCY VIRAL SYMPTOM CLUSTERS - Tascilar, Koray; Simon, David; Krönke, Gerhard; Kleyer, Arnd; Ramming, Andreas; Atreya, Raja; Tenbusch, Matthias; Überla, Klaus; Berking, Carola; Sticherling, Michael; Neurath, Markus; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Paucity of viral infection symptoms in patients with immune-mediated inflammatory diseases. - Yalcin-Mutlu, Melek; Kleyer, Arnd; Krönke, Gerhard; Fagni, Filippo; Temiz, Selahattin Alp; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Schönau, Verena; Bohr, Daniela; Schuster, Louis; et al. (BMJ Open, 2025)
OBJECTIVES: Although patients with immune-mediated inflammatory diseases (IMID) are thought to be more susceptible to viral infections, it is unclear whether their presentation differs between patients with IMID and healthy controls. This study aimed to investigate the symptom pattern of common viral infections in patients with IMID and compare it with controls without IMIDs. DESIGN: A cross-sectional study conducted between 1 February and 30 April 2020, using a questionnaire. SETTING: Seven tertiary regional care centers in Germany, which specialised in the care of patients with IMID (namely, in gastroenterology, dermatology, rheumatology and immunology clinical care). PARTICIPANTS: One thousand nine hundred nine participants completed the survey (757 patients with IMID; 1152 non-IMID controls). PRIMARY OUTCOME MEASURE: The occurrence of 11 common viral illness symptoms within the preceding 3 months in patients with IMID and non-IMID controls. RESULTS: Symptom data were clustered, based on number and co-occurrance, into 3 major clusters and 2 subclusters ranked by the average number of symptoms. Patients with inflammatory bowel disease and psoriasis were significantly overrepresented in the lower-frequency subcluster of the polysymptomatic cluster. Patients with rheumatoid arthritis were overrepresented in the lower-frequency subclusters of the intermediate and oligo-/asymptomatic clusters. Controls were over-represented only in the higher-frequency subclusters of each major cluster where none of the IMIDs were over-represented. Spondyloarthritis and other IMIDs were also overrepresented in the low-frequency subcluster, but the results were not significant. Overall, patients with rheumatoid arthritis patients reported fewer symptoms (rate ratio=0.68, 95% CI, 0.59 to 0.80) than non-IMID controls. CONCLUSION: Patients with IMID are over-represented in low-frequency subclusters, even among individuals who have reported a broad range of viral infection symptoms. This pattern suggests that the manifestations of viral infections are different between patients with IMID and controls, thus challenging the accurate and early diagnosis of infections.
EVALuna2:581658

Pemphigus Foliaceous With Secondary Herpes Simplex Infection - Koch, Elias; Sticherling, Michael; Wagner, Nicola (JAMA Dermatology, 2025)
CRIS-Team Scopus Importer:2025-11-28

Perception of the coronavirus pandemic by patients with atopic dermatitis - Results from the TREATgermany registry - Helmert, Claudia; Siegels, Doreen; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Kleinheinz, Andreas; Harder, Inken; Schaekel, Knut; Effendy, Isaak; Wollenberg, Andreas; Sticherling, Michael; Stahl, Maren; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background TREATgermany, a registry for patients with moderate to severe atopic dermatitis (AD), established an additional questionnaire in spring 2020 to investigate the effects of the coronavirus pandemic on the daily life of patients with AD. Material and Methods A questionnaire was used to analyze general information regarding a patient's experience of the coronavirus pandemic and, using the Inventory of Life-Changing Events, the resulting personal burden. To analyze possible associations between disease severity (EASI score, oSCORAD, IGA, PGA, POEM), quality of life (DLQI) and personal burden, t-tests, analyses of variance and correlations were evaluated, controlled for sex and age. Results 58 % (n = 233) of the included 400 registry patients reported high burden scores caused by the coronavirus pandemic, regardless of an actual infection. Men showed significantly higher burden scores than women, and younger than older respondents (both P = 0.03). There were no differences in burden scores related to the physician's assessment of disease severity. However, patients with higher quality of life impairments and higher disease severity perceived the burden of the coronavirus pandemic as less severe (DLQI P = 0.019, PGA P = 0.044). Conclusions Our data show that registry patients considered the coronavirus pandemic as a life-changing event and perceived the burden differently. This should be taken into account in the treatment of patients with moderate to severe AD as well as in further studies.
CRIS-Team WoS Importer:2022-01-07

Physician-reported Clinical Unmet Needs, Burden and Treatment Patterns of Paediatric Psoriasis Patients: A US and EU Real-world Evidence Study - Seyger, Marieke M.B.; Augustin, Matthias; Sticherling, Michael; Bachhuber, Teresa; Fang, Juanzhi; Hetherington, James; Lucas, James; Meakin, Sophie; Richardson, Craig; Paller, Amy S. (Acta Dermato-Venereologica, 2022)
This study is a retrospective analysis using data col-lected from the Adelphi Paediatric Psoriasis Disease-Specific Programme cross-sectional survey. Despite being treated for their psoriasis, a substantial proportion of paediatric patients presented with moderate (18.3%) or severe (1.3%) disease at sampling; 42.9% and 92.0% had a body surface area (BSA) of >10%, and 38.8% and 100.0% had a Psoriasis Area Severity Index (PASI) score >10, respectively. Overall, 69.9% of patients had only ever been treated with a topical therapy for their psoriasis. For patients with moderate or severe disease at sampling, 16.3% and 14.4% were currently receiving conventional systemics or biologic therapy, respectively. There is a clinical unmet need in this paediatric population; a considerable percen-tage of patients still experienced moderate or severe disease and persistent psoriasis symptoms, with nu-merous body areas affected. A significant proportion of patients were undertreated, which may explain the high burden of disease observed.
CRIS-Team Scopus Importer:2022-04-15
Keywords: clinical characteristics; paediatric psoriasis; point-in-time sur-vey; psoriasis; real-world; unmet needs

Pooled safety analysis from two phase III studies of secukinumab in paediatric patients with moderate-to-severe plaque psoriasis up to week 52 - Sticherling, Michael; Nikkels, A. F.; Hamza, A. M.; Kwong, P.; Ortmann, C. -E.; Papanastasiou, P.; Forrer, P.; Keefe, D. (BRITISH JOURNAL OF DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-01-14

Proactive Management with twice-a-week Use of topical Cal/BD Spray Foam Management extends the Effectiveness of the Treatment in Comparison to Reactive Management in Patients with Plaque Psoriasis - Stein-Gold, L.; Alonso-Llamazares, J.; Laws, P.; Perrussel, M.; Yamauchi, P.; Thoning, H.; Toxvaerd, C.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Prospective study in bullous pemphigoid: association of high serum anti-BP180 IgG levels with increased mortality and reduced Karnofsky score - Holtsche, M. M.; Goletz, S.; Van Beek, N.; Zillikens, Detlef; Benoit, S.; Harman, K.; Walton, S.; English, J.; Sticherling, Michael; Chapman, A.; Levell, N. J.; Groves, R.; et al. (British Journal of Dermatology, 2018)
BACKGROUND: Bullous pemphigoid (BP) is a subepidermal blistering disease characterized by autoantibodies against the two hemidesmosomal proteins, BP180 (type XVII collagen) and BP230. The multicentre prospective BLISTER (Bullous Pemphigoid Steroids and Tetracyclines) trial randomized 253 patients with BP to compare the benefits and harms between initial treatment with doxycycline or prednisolone. OBJECTIVES: To analyse distinct autoantibody profiles for the prediction of the disease course in a well-characterized cohort of BP sera. METHODS: One hundred and forty-three patients of the BLISTER trial consented to participate in this serological study. Sera taken at baseline were analysed by (i) indirect immunofluorescence, (ii) anti-BP180 NC16A (16th noncollagenous domain) and anti-BP230 enzyme-linked immunosorbent assay and (iii) immunoblotting with various substrates. Results were then linked with clinical parameters including age, Karnofsky score, number of blisters, related adverse events and mortality. RESULTS: Disease activity correlated with immunoglobulin (Ig)G anti-BP180 levels but not with levels of anti-BP230 IgG and anti-BP180 IgE. High levels of both anti-BP180 IgG and anti-BP230 IgG were associated with a low Karnofsky score. The presence of anti-BP230 IgG was more frequent in older patients. Those with higher total IgE serum levels suffered from fewer adverse events. Higher IgG anti-BP180 levels were associated with an increased 1-year mortality rate. CONCLUSIONS: Analysis of the autoantibody profile is not only of diagnostic relevance but may also be helpful in predicting the course of the disease.
EVALuna2:34763

Pruritus in Psoriasis - Correlation to the Severity of the clinical appearance of the Skin? - Achterberg, Fritz Leonard; Kremer, Andreas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psoriasis and autoimmunity - Sticherling, Michael (Autoimmunity Reviews, 2016)
Psoriasis is one of the most common chronic inflammatory human skin diseases. Though clinically well characterized, the exact etiological and pathogenic mechanisms are still not known in detail. Current knowledge indicates distinct overlap to other inflammatory as well as autoimmune disorders. However, the one or more relevant autoantigens could not be characterized so-far. On the other side, several autoimmune diseases were shown to be associated with psoriasis. In addition, serological autoimmune phenomena, namely diverse circulating specific autoantibodies could be demonstrated in the past. A matter of current debate is if psoriasis is a primary autoimmune disease or secondarily evolving into autoimmunity as seen in other chronic inflammatory diseases. Related to this aspect is the concept of autoinflammation versus autoimmunity where psoriasis shares mechanisms of both entities. Though T-cells remain among the most important cellular players in the pathogenesis of psoriasis and current therapeutic strategies successfully target these cells or their products irrespective of these concepts, autoimmunity if relevant will add to the treatment armamentarium by using protective and prophylactic antigen-specific modalities.
EVALuna2:19626

Psoriasis as a Manifestation of an Immune Reconstitution in Two Patients with Hepatitis C Treated with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2017)
EVALuna2:34349

Psoriasis capitis and seborrhoic eczema of scalp diseases - Sticherling, Michael (Hautarzt, 2017)
The scalp may be affected by various diseases with equally varying manifestations. Erythema and scaling is often accompanied by agonizing itch. Scalp psoriasis and seborrheic eczema represent the most frequent diseases, which can be differentiated into classical cases; however, overlap and similarities are seen. Sharply demarcated erythematosquamous plaques across the natural hairline in psoriasis are opposed to blurred dark-red erythema and yellowish, greasy scales in seborrheic eczema. Whereas with the latter diffuse alopecia may frequently be found, hair loss is rarely seen in psoriasis and may also be related to therapeutic agents. Treatment is based on acuity as well as extent of disease and individual life quality aspects of the patients. It is mainly based on topical corticosteroids, combined with vitamin D derivatives in psoriasis and antimycotic agents in seborrheic eczema. In severe cases and widespread psoriatic disease, systemic treatment may be necessary, including the classic agents methotrexate, fumarates and ciclosporin as well as biologicals. Systemic treatment of seborrheic eczema is rarely necessary and resides on corticosteroids, antimycotic agents and vitamin A derivatives. In addition, intensive counseling of patients on the necessity of consequent and long-term treatment as well as use of mild skin care products is mandatory.
EVALuna2:34347

Psoriasis in children: a single center analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psoriasis in children: a single-centre analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (2017)
EVALuna2:34339

Psoriasis in routine clinical care: Complete skin clearance rates with guselkumab increase through week 52-Results from the real-life PERSIST study - Hoffmann, Matthias; Sticherling, Michael; Korge, Bernhard; Mortazawi, Dariusch; Personke, Yvonne; Gomez, Mario; Wegner, Sven; Gerdes, Sascha (JOURNAL OF THE AMERICAN ACADEMY OF DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-08-27

Psoriasis - Occurrence and Reality: Disease of the Psoriasis Group - Leupolz, S.; Sticherling, Michael (2017)
EVALuna2:34353

Psoriasis vulgaris as Manifestation of Immune Reconstitution in Patients with Hepatitis C under Treatment with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34350

Psoriatic arthritis epidemiology, comorbid disease profiles and risk factors: Results from a claims database analysis - Rech, Jürgen; Sticherling, Michael; Stoessel, Daniel; Biermann, Mona H.C.; Häberle, Benjamin M.; Reinhardt, Maximilian (Rheumatology Advances in Practice, 2020)
Objective. Psoriasis is a systemic inflammatory disease often accompanied by comorbidities, including metabolic syndrome, cardiovascular diseases and depression. Up to 41% of psoriasis patients develop psoriatic arthritis (PsA), making it one of the most relevant manifestations. A large health claims data set was analysed to determine the rate of PsA development in psoriasis patients. Furthermore, comorbid disease profiles of psoriasis patients with or without PsA were compared, and potential risk factors for the development of PsA were identified. Methods. This was a non-interventional, retrospective analysis of anonymized insurance health claims data using a subset of the Institute of Applied Health Research Berlin (InGef) database. The primary outcome was the prevalence and incidence of diagnosed PsA among psoriasis patients in Germany. Risk factors for the development of PsA in psoriasis patients were determined by conditional logistic regression analysis. Results. The cumulative percentage of patients with existing psoriasis developing concomitant PsA over 4 years was 3.44%, with a mean time to diagnosis of PsA of 1.5 years. Psoriasis patients diagnosed with acute rheumatism (odds ratio: 2.93, 95% CI=1.76, 4.86; P<0.001) or pain in unspecific joints (odds ratio: 1.74, 95% CI=1.01, 2.99; P=0.047) showed an increased risk for development of PsA later on. Interestingly, fewer than half of the patients with concomitant PsA consulted a rheumatologist. Conclusions. Unspecific arthritic symptoms are likely to precede PsA diagnoses and can develop soon after onset of psoriasis, with accumulating risk over time. There is a high unmet need for early rheumatological assessment of psoriasis patients.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Comorbid disease; Epidemiology; Incidence; Insurance health claims data; PsA; Psoriasis; Risk factors

Psoriatic Arthritis - Epidemiology, Incidence Rate in Psoriasis Patients, Comorbidity Profiles and Risk Factor Analysis - Rech, Jürgen; Sticherling, Michael; Biermann, Mona; Haeberle, Benjamin; Reinhardt, Maximilian (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Quantitative and Qualitative Changes of Bone in Psoriasis and Psoriatic Arthritis Patients - Kocijan, Roland; Englbrecht, Matthias; Haschka, Judith; Simon, David; Kleyer, Arnd; Finzel, Stephanie; Kraus, Sebastian; Resch, Heinrich; Muschitz, Christian; Engelke, Klaus; Sticherling, Michael; Rech, Jürgen; et al. (Journal of Bone and Mineral Research, 2015)
Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by periarticular bone loss and new bone formation. Current data regarding systemic bone loss and bone mineral density (BMD) in PsA are conflicting. The aim of this study was to evaluate bone microstructure and volumetric BMD (vBMD) in patients with PsA and psoriasis. We performed HR-pQCT scans at the ultradistal and periarticular radius in 50 PsA patients, 30 psoriasis patients, and 70 healthy, age- and sex-related controls assessing trabecular bone volume (BV/TV), trabecular number (Tb.N), inhomogeneity of the trabecular network, cortical thickness (Ct.Th), and cortical porosity (Ct.Po), as well as vBMD. Trabecular BMD (Tb.BMD, p = 0.021, 12.0%), BV/TV (p = 0.020, -11.9%), and Tb.N (p = 0.035, 7.1%) were significantly decreased at the ultradistal radius and the periarticular radius in PsA patients compared to controls. In contrast, bone architecture of the ultradistal radius and periarticular radius was similar in patients with psoriasis and healthy controls. Duration of skin disease was associated with low BV/TV and Tb.N in patients with PsA. These data suggest that trabecular BMD and bone microstructure are decreased in PsA patients. The observation that duration of skin disease determines bone loss in PsA supports the concept of subclinical musculoskeletal disease in psoriasis patients. © 2015 American Society for Bone and Mineral Research.
EVALuna2:10104

Real-world data on the effectiveness, safety and drug survival of dupilumab: an analysis from the TREATgermany registry - Stoelzl, Dora; Sander, Nicole; Heratizadeh, Annice; Haufe, Eva; Harder, Inken; Abraham, Susanne; Heinrich, Luise; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Schaekel, Knut; Ertner, Konstantin; et al. (British Journal of Dermatology, 2022)
CRIS-Team Scopus Importer:2022-11-11

Real-world effectiveness of guselkumab in patients with psoriasis: Health-related quality of life and efficacy data from the noninterventional, prospective, German multicenter PERSIST trial - Gerdes, Sascha; Bräu, Beate; Hoffmann, Matthias; Korge, Bernhard; Mortazawi, Dariusch; Wiemers, Franca; Wegner, Sven; Personke, Yvonne; Gomez, Mario; Sticherling, Michael (Journal of Dermatology, 2021)
Psoriasis is a common, chronic inflammatory skin disorder negatively impacting health-related quality of life (HRQoL). Guselkumab, targeting interleukin-23 (IL-23), is an approved biologic therapy for psoriasis. PERSIST is an ongoing prospective, noninterventional, long-term, German multicenter study evaluating the effect of guselkumab on HRQoL, and its efficacy and safety in patients with moderate-to-severe psoriasis in a real-world setting. The primary endpoint is the proportion of patients with a Dermatology Life Quality Index (DLQI) score ≤ 1 at week 28. Of 303 patients enrolled and treated with guselkumab, mean age and disease duration were 49.7 and 21.0 years, respectively, and 51.2% (n = 155) of patients had received ≥1 prior biologic therapy. Mean baseline DLQI score was 13.7, and mean symptom and sign scores in the Psoriasis Symptoms and Signs Diary (PSSD) were 51.9 and 60.8, respectively. Baseline Psoriasis Area Severity Index (PASI) and body surface area (%) scores were 16.4 and 27.5. Following 28 weeks of guselkumab treatment, the mean DLQI score decreased to 2.8, and 56.8% of patients (n = 150) achieved DLQI ≤ 1. Mean PSSD symptom and sign scores also improved, decreasing to 12.5 and 15.9, respectively. At week 28, PASI 90 response was 55.3%; significant improvement was observed in patients with psoriasis in difficult-to-treat areas. Overall, analyses demonstrated that guselkumab was effective in the real-world setting, as measured by HRQoL and skin improvements, even in patients with a high burden of disease and those who have received multiple biologic therapies. No new safety signals were observed.
CRIS-Team Scopus Importer:2021-09-17
Keywords: anogenital; guselkumab; palmoplantar; psoriasis; quality of life; RWE; scalp

Real-world evidence from the non-interventional, prospective, German multicentre PERSIST study of patients with psoriasis after 1 year of treatment with guselkumab - Gerdes, S.; Asadullah, K.; Hoffmann, M.; Korge, B.; Mortazawi, D.; Wegner, S.; Personke, Y.; Gomez, M.; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: PERSIST was a prospective, non-interventional, long-term, German multicentre study of patients with moderate-to-severe psoriasis receiving guselkumab, an approved monoclonal antibody that binds to the p19 subunit of interleukin (IL)-23, in a real-world setting. Objectives: Evaluation of the efficacy and safety of guselkumab, and its effect on health-related quality of life (HRQoL), in patients with moderate-to-severe psoriasis who have received 52 weeks of treatment. Methods: Patients (≥18 years old) were prescribed guselkumab as per routine clinical practice. End points assessed include Psoriasis Area and Severity Index (PASI), Physician's Global Assessment (PGA), target Nail Psoriasis Severity Index (NAPSI), and the Dermatology Life Quality Index (DLQI). Results: Overall, 303 patients were enrolled and treated with guselkumab. Mean disease duration was 21.0 years, and 77.2% and 51.2% of patients had received ≥1 prior conventional systemic or ≥1 prior biologic therapy, respectively. Mean PASI score decreased from 16.4 at baseline to 3.0 by Week (W) 28, and further decreased to 2.4 by W52, while the proportion of patients achieving an absolute PASI score of ≤1 increased from 1.3% at baseline, to 50.8% at W28 and to 58.4% by W52. PASI90 and PASI100 responses also showed marked improvements between W28 and W52, regardless of biologic treatment history. Clearance of psoriatic skin was observed in difficult-to-treat areas, with the percentage of patients achieving a PGA score ≤1 increasing between W28 and W52. Guselkumab improved HRQoL; mean DLQI score decreased from 13.7 at baseline to 2.8 by W28, and further decreased to 2.4 by W52. At W52, 64.6% of patients achieved a DLQI score ≤1. The cumulative probability of drug survival was 92.4% at W52. Conclusions: Guselkumab is efficacious and well tolerated regardless of previous biologic therapies, comorbidities or psoriasis manifestation in difficult-to-treat areas. No new safety signals were observed.
CRIS-Team Scopus Importer:2022-06-03

Resolution of synovitis and arrest of catabolic and anabolic bone changes in patients with psoriatic arthritis by IL-17A blockade with secukinumab: results from the prospective PSARTROS study - Kampylafka, Eleni; D'Oliveira, Isabelle; Linz, Christina; Lerchen, Veronika; Stemmler, Fabian; Simon, David; Englbrecht, Matthias; Sticherling, Michael; Rech, Juergen; Kleyer, Arnd; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2018)
BACKGROUND: Although the effects of interleukin-17A (IL-17A) inhibition on the signs and symptoms of psoriatic arthritis (PsA) are well defined, little is known about its impact of local inflammatory and structural changes in the joints. The PSARTROS study was designed to elucidate the effects of IL-17A inhibition on inflammation and bone changes in joints affected by PsA. METHODS: This was a prospective open-label study in 20 patients with active PsA receiving 24 weeks of treatment with the IL-17A inhibitor secukinumab. Magnetic resonance imaging (MRI), power Doppler ultrasound (PDUS), and high-resolution peripheral quantitative computer tomography (HR-pQCT) of the hands were performed at baseline and after 24 weeks to assess synovitis, periarticular inflammation, bone erosion, enthesiophyte formation, and bone structure. Demographic and clinical measures of joint disease (DAPSA and DAS28-ESR), skin disease (PASI and BSA), and composite measures (minimal disease activity, or MDA) were also recorded. RESULTS: Treatment with secukinumab led to significant improvement of signs and symptoms of PsA; 46% reached MDA and 52% DAPSA low disease activity. MRI synovitis (P = 0.034) and signal in PDUS (P = 0.030) significantly decreased after 24 weeks of treatment. Bone erosions in MRI and HR-pQCT and enthesiophytes in the HR-pQCT did not show any progression, and structural integrity and functional bone strength remained stable. CONCLUSIONS: IL-17 inhibition by secukinumab over 24 weeks led to a significant decrease of synovial inflammation and no progression of catabolic and anabolic bone changes in the joints of patients with PsA. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02483234 , June 26, 2015; retrospectively registered.
EVALuna2:34447

Retrospective analysis of autoimmune bullous diseases in Middle Franconia - Sollfrank, Lukas; Schönfelder, Valerie; Sticherling, Michael (Frontiers in Immunology, 2023)
Introduction: Autoimmune bullous diseases (AIBDs) are a group of rare cutaneous disorders affecting cornified skin and mucous membranes. They are characterized by tense or flaccid blistering and erosions due to autoantibodies against desmosomal and hemidesmosomal structural proteins of the skin. This group of disorders can be divided into those of pemphigoid and those of pemphigus diseases. If left untreated, these autoimmune diseases can cause serious or even life-threatening complications such as loss of fluid, superinfections or impaired food intake. Due to modern standardized serological assays, the diagnosis of AIBDs can usually be confirmed in combination with their clinical appearance. Whereas for a long time corticosteroids were the major players in the treatment of these diseases, with the approval of rituximab and other immunosuppressive agents, the therapy has increasingly improved. Methods: In this study, we aimed to investigate epidemiologic and clinical features as well as diagnostics and therapy of bullous autoimmune diseases in Middle Franconia, a governorate within the German federal state of Bavaria. Patients diagnosed or treated because of a AIBDs between 01.04.2013 and 31.03.2019 at the dermatological department of the university hospital Erlangen were included in this retrospective study (n = 242). Patients were either diagnosed for the first time (n=176) or the diagnosis has been confirmed (n=66) at the department. The respective incidence was calculated among the 176 subjects who had been diagnosed at the center in this period. Data was taken from patient records and analyzed with Microsoft® Excel. The evaluation included the diagnoses of pemphigus vulgaris (PV), pemphigus foliaceus (PF), bullous pemphigoid (BP), mucous membrane pemphigoid (MMP), linear IgA dermatosis (LAD), epidermolysis bullosa acquisita (EBA), and dermatitis herpetiformis (DH). Results: This study shows that the incidence of each AIBDs in Middle Franconia is low and comparable (PV, PF, LAD, EBA) or lower (BP, MMP, DH) than in other studies and regions. BP is the most common newly diagnosed AIBD in Middle Franconia. Discussion: Due to the chronic and sometimes severe course of AIBDs, repeated in-house treatments are often necessary. To date, mainly topically and systemically applied corticosteroids in combination with immunomodulators are used as first-line therapy.
CRIS-Team Scopus Importer:2023-11-03
Keywords: autoimmune bullous dermatoses; bullous dermatoses; bullous pemphigod; epidemiology; pemphigoid diseases; pemphigus diseases

S100A8 BUT NOT S100A9 LEVEL IS RELATED TO THE EXTENT OF EROSIVE BONE DAMAGE IN PSORIATIC ARTHRITIS PATIENTS - Simon, David; Nas, K.; Faustini, F.; Kleyer, Arnd; Haschka, J.; Englbrecht, Matthias; Hueber, Axel; Kocijan, R.; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2016)
EVALuna2:13430

S2k guideline: Diagnosis and management of cutaneous lupus erythematosus - Part 1: Classification, diagnosis, prevention, activity scores - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Günther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Mueller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team WoS Importer:2021-08-27

S2k guideline: Diagnosis and management of cutaneous lupus erythematosus – Part 2: Therapy, risk factors and other special topics - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Gunther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Muller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-08-13

S2k Guideline for the diagnosis and treatment of mucous membrane pemphigoid - Hofmann, Silke C.; Gunther, Claudia; Bockle, Barbara C.; Didona, Dario; Ehrchen, Jan; Gaskins, Matthew; Geerling, Gerd; Glaser, Regine; Hadaschik, Eva; Hampl, Monika; Habkamp, Pia; Jackowski, Jochen; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Mucous membrane pemphigoid (MMP) is a pemphigoid disease with predominant mucous membrane involvement. It mainly affects the mucous membranes of the mouth, eyes, nose and pharynx, but also the larynx, trachea, esophagus, genital and perianal regions. The manifestation of the disease covers a wide spectrum from gingival erythema and single oral lesions to severe tracheal strictures that obstruct breathing and conjunctival scarring with marked visual impairment and, not infrequently, blindness. In addition to a clinical picture of predominant mucosal involvement, diagnosis is based on direct immunofluorescence of a peri-lesional biopsy and serology. The main target antigen is BP180 (collagen XVII), and reactivity with laminin 332 is associated with malignancy in approximately 25 % of MMP patients. The treatment of MMP is challenging. On the one hand, due to the involvement of different mucous membranes, good interdisciplinary cooperation is required; on the other hand, due to the rarity of the disease, no randomized controlled clinical trials are available. The aim of this guideline is to present the clinical picture, including severity and scoring systems, and to give guidance for diagnosing and treating this complex disease. In MMP, interdisciplinary cooperation plays an essential role as well as the prompt diagnosis and initiation of adequate therapy in order to avoid irreversible damage to the mucous membranes with serious complications.
CRIS-Team WoS Importer:2022-11-25

S2k guideline for the diagnosis of pemphigus vulgaris/foliaceus and bullous pemphigoid - Schmidt, Enno; Goebeler, Matthias; Hertl, Michael; Sardy, Miklos; Sitaru, Cassian; Eming, Ruediger; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Orzechowski, Hans-Dieter; Pfeiffer, Christiane; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
EVALuna2:19565

S2k guidelines for the treatment of pemphigus vulgaris/foliaceus and bullous pemphigoid: 2019 update - Schmidt, Enno; Sticherling, Michael; Sárdy, Miklós; Eming, Rüdiger; Goebeler, Matthias; Hertl, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Nast, Alexander; Orzechowski, Hans Dieter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-26

S2k guidelines for the treatment of pemphigus vulgaris/foliaceus and bullous pemphigoid - Eming, Ruediger; Sticherling, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Pfeiffer, Christiane; Schuster, Volker; Zillikens, Detlef; Goebeler, Matthias; Hertl, Michael; Nast, Alexander; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
EVALuna2:19564

S2k guidelines for the treatment of psoriasis in children and adolescents – Short version part 1 - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology, pediatrics, pediatric dermatology and pediatric rheumatology as well as policymakers and insurance funds. They were developed by dermatologists and pediatric dermatologists in collaboration with pediatric rheumatologists using a formal consensus process (S2k). The guidelines highlight topics such as disease severity, quality of life, treatment goals as well as problems associated with off-label drug therapy in children. Trigger factors and diagnostic aspects are discussed. The primary focus is on the various topical, systemic and UV-based treatment options available and includes recommendations for use and treatment algorithms. Other aspects addressed herein include vaccinations in children and adolescents with psoriasis as well as various disease subtypes such as guttate psoriasis, diaper psoriasis, pustular psoriasis and psoriatic arthritis. Finally, we also provide recommendations for imaging studies and the diagnostic workup to rule out tuberculosis prior to initiating systemic treatment. Note: This article constitutes part 1 of the Sk2 guidelines for the treatment of psoriasis in children and adolescents. Part 2 will be published in the next issue. It contains chapters on UV therapy, systemic treatment, tonsillectomy and antibiotics, vaccinations, guttate psoriasis, psoriatic arthritis, complementary medicine, as well as imaging studies and diagnostic workup to rule out tuberculosis prior to systemic treatment.
CRIS-Team Scopus Importer:2019-08-30

S2k guidelines for the treatment of psoriasis in children and adolescents - Short version part 2. - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Foelster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Hoeger, Peter; Horneff, Gerd; Von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology, pediatrics, pediatric dermatology and pediatric rheumatology as well as policymakers and insurance funds. They were developed by dermatologists and pediatric dermatologists in collaboration with pediatric rheumatologists using a formal consensus process (S2k). The guidelines highlight topics such as disease severity, quality of life, treatment goals as well as problems associated with off-label drug therapy in children. Trigger factors and diagnostic aspects are discussed. The primary focus is on the various topical, systemic and UV-based treatment options available and includes recommendations for use and treatment algorithms. Other aspects addressed herein include vaccinations in children and adolescents with psoriasis as well as various disease subtypes such as guttate psoriasis, diaper psoriasis, pustular psoriasis and psoriatic arthritis. Finally, we also provide recommendations for imaging studies and the diagnostic workup to rule out tuberculosis prior to initiating systemic treatment. Note: This article constitutes part 2 of the Sk2 guidelines for the treatment of psoriasis in children and adolescents. Part 1 was published in last month's issue. It contained introductory remarks and addressed aspects of diagnosis and topical treatment.
EVALuna2:212834

S2k-Leitlinie zur Diagnostik und Therapie des kutanen Lupus erythematodes – Teil 1: Klassifikation, Diagnostik, Prävention und Aktivitätsscores - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Günther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Müller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-09-17

S2k-Leitlinie zur Therapie der Psoriasis bei Kindern und Jugendlichen – Kurzfassung Teil 1 - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
CRIS-Team Scopus Importer:2019-08-30

S2k-Leitlinie zur Therapie der Psoriasis bei Kindern und Jugendlichen - Kurzfassung Teil 2. - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Diese Leitlinie richtet sich an Assistenz- und Fachärzte der Dermatologie, Pädiatrie, Kinderdermatologie und Kinderrheumatologie sowie an Kostenträger und politische Entscheidungsgremien. Die Leitlinie wurde im formellen Konsensusverfahren (S2k) von Dermatologen und Kinderdermatologen unter Einbindung von Kinderrheumatologen erstellt. Die Leitlinie stellt einen Überblick über Schweregrad, Lebensqualität und Therapieziele mit Erläuterung der Off-Label-Problematik im Kindesalter dar. Es werden Diagnosestellung und Triggerfaktoren erläutert. Der Schwerpunkt der Leitlinie liegt auf der Darstellung der verschiedenen topischen Therapien, UV-Therapien und systemischen Therapieoptionen mit Abbildung der Empfehlungen zur Anwendung der Therapien sowie Therapiealgorithmen. Darüber hinaus wird im Kontext auf Impfungen bei Psoriasis im Kindesalter sowie auf verschiedene Sonderformen wie Psoriasis guttata, Windelpsoriasis, Psoriasis pustulosa und Psoriasisarthritis eingegangen. Auch werden Empfehlungen zu Tuberkulosediagnostik und Röntgenuntersuchung vor Systemtherapie gegebe
EVALuna2:212833

S2k-Leitlinie zur Therapie des Pemphigus vulgaris/foliaceus und des bullösen Pemphigoids: 2019 Update - Schmidt, Enno; Sticherling, Michael; Sárdy, Miklós; Eming, Rüdiger; Goebeler, Matthias; Hertl, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Nast, Alexander; Orzechowski, Hans Dieter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-22

SARS-CoV-2 Transmission from Presymptomatic Meeting Attendee, Germany - Hijnen, Dirkjan; Marzano, Angelo Valerio; Eyerich, Kilian; Geurtsvankessel, Corine; Giménez-Arnau, Ana Maria; Joly, Pascal; Vestergaard, Christian; Sticherling, Michael; Schmidt, Enno (Emerging Infectious Diseases, 2020)
During a meeting in Munich, Germany, a presymptomatic attendee with severe acute respiratory syndrome coronavirus 2 infected at least 11 of 13 other participants. Although 5 participants had no or mild symptoms, 6 had typical coronavirus disease, without dyspnea. Our findings suggest hand shaking and face-to-face contact as possible modes of transmission.
CRIS-Team WoS Importer:2020-08-07

SARS-CoV-2 vaccination responses in untreated, conventionally treated and anticytokine-treated patients with immune-mediated inflammatory diseases - Simon, David; Tascilar, Koray; Fagni, Filippo; Krönke, Gerhard; Kleyer, Arnd; Meder, Christine; Meder, Christine; Atreya, Raja; Leppkes, Moritz; Kremer, Andreas E.; Pachowsky, Milena; Schuch, Florian; et al. (Annals of the Rheumatic Diseases, 2021)
Objectives: To better understand the factors that influence the humoral immune response to vaccination against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods: Patients and controls from a large COVID-19 study, with (1) no previous history of COVID-19, (2) negative baseline anti-SARS-CoV-2 IgG test and (3) SARS-CoV-2 vaccination at least 10 days before serum collection were measured for anti-SARS-CoV-2 IgG. Demographic, disease-specific and vaccination-specific data were recorded. Results: Vaccination responses from 84 patients with IMID and 182 controls were analysed. While all controls developed anti-SARS-CoV-2 IgG, five patients with IMID failed to develop a response (p=0.003). Moreover, 99.5% of controls but only 90.5% of patients with IMID developed neutralising antibody activity (p=0.0008). Overall responses were delayed and reduced in patients (mean (SD): 6.47 (3.14)) compared with controls (9.36 (1.85); p<0.001). Estimated marginal means (95% CI) adjusted for age, sex and time from first vaccination to sampling were 8.48 (8.12-8.85) for controls and 6.90 (6.45-7.35) for IMIDs. Significantly reduced vaccination responses pertained to untreated, conventionally and anticytokine treated patients with IMID. Conclusions: Immune responses against the SARS-CoV-2 are delayed and reduced in patients with IMID. This effect is based on the disease itself rather than concomitant treatment.
CRIS-Team Scopus Importer:2021-05-21
Keywords: biological therapy; COVID-19; epidemiology; vaccination

SCLE manifestation after mRNA COVID-19 vaccination - Rechtien, Laura; Erfurt-Berge, Cornelia; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2022)
CRIS-Team WoS Importer:2022-01-14

Secondary syphilis infection under treatment with ustekinumab - Uslu, Ugur; Heppt, Franz; Sticherling, Michael (Clinical and Experimental Dermatology, 2017)
EVALuna2:34342

Secukinumab 2-weekly vs. 4-weekly dosing in patients with plaque-type psoriasis: results from the randomized GAIN study - Reich, K.; Koerber, A.; Mrowietz, U.; Sticherling, Michael; Sieder, C.; Frueh, J.; Bachhuber, T. (British Journal of Dermatology, 2020)
Background: Secukinumab is a fully human monoclonal antibody that selectively neutralizes interleukin-17A and shows long-lasting efficacy and safety in plaque psoriasis. More evidence is required to optimize secukinumab dosing according to clinical response. Objectives: GAIN compared the efficacy and safety of secukinumab 300 mg every 2 weeks (q2w) with 300 mg every 4 weeks (q4w) in patients achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) but not PASI 90 after 16 weeks. Methods: In total, 772 patients with moderate-to-severe plaque psoriasis received secukinumab 300 mg subcutaneously at baseline and weeks 1, 2, 3 and 4, then q4w until week 16. At week 16, patients with PASI ≥ 75 to PASI < 90 were randomized 1: 1 to continue q4w dosing (n = 162) or switch to q2w (n = 163) to week 32. The primary endpoint was superiority of q2w to q4w dosing for PASI 90 response at week 32. Results: PASI 90 response at week 32 was numerically greater with secukinumab 300 mg q2w than with secukinumab 300 mg q4w in suboptimal responders, but this did not reach statistical significance (64·4% vs. 57·4%; odds ratio 0·64, 95% confidence interval 0·39–1·07; P = 0·087). Although the primary endpoint was not met, absolute PASI was significantly lower at week 32 in q2w vs. q4w patients (2·11 vs. 2·84, P = 0·024). Significantly more patients with q2w vs. q4w dosing showed minimal disease activity (Investigator’s Global Assessment score 0 or 1: 73·0% vs. 64·1%, P < 0·05) and improved quality of life (Dermatology Life Quality Index score 0 or 1: 58·9% vs. 50·6%, P < 0·05) at week 32. No new or unexpected safety signals arose. Conclusions: Most patients achieved PASI 90 response with secukinumab q4w. There was potential benefit of q2w dosing in some suboptimal responders. Continued q4w treatment can improve response even after 16 weeks.
CRIS-Team Scopus Importer:2020-12-04

Secukinumab in adult patients with lichen planus: efficacy and safety results from the randomized placebo-controlled proof-of-concept PRELUDE study. - Passeron, Thierry; Reinhardt, Maximilian; Ehst, Benjamin; Weiss, Jonathan; Sluzevich, Jason; Sticherling, Michael; Reygagne, Pascal; Wohlrab, Johannes; Hertl, Michael; Fazel, Nasim; Muscianisi, Elisa; Fan, Heng; et al. (British Journal of Dermatology, 2024)
BACKGROUND: Patients with lichen planus (LP) refractory to available therapies often experience a high disease burden, representing a population with a clear unmet need for new treatments. OBJECTIVES: To evaluate the efficacy and safety of secukinumab 300 mg over 32 weeks in adult patients with biopsy-proven cutaneous LP (CLP), mucosal LP (MLP) or lichen planopilaris (LPP) that is inadequately controlled by topical corticosteroids. METHODS: PRELUDE was a randomized double-blind placebo-controlled phase II proof-of-concept study that enrolled patients with CLP, MLP or LPP. Eligible patients were randomized to either secukinumab 300 mg every 4 weeks for 32 weeks (SECQ4W) or placebo for 16 weeks followed by secukinumab 300 mg every 2 weeks (SECQ2W) for 16 weeks. The primary endpoint was achievement of the newly designed Investigator's Global Assessment (IGA) score ≤ 2 at week 16. RESULTS: Overall, 111 patients were randomized (n = 37 each) to CLP, MLP and LPP cohorts. As the proof-of-concept criteria were not met for any of the three cohorts, the primary objective was not met. A numerically higher proportion of patients achieved IGA ≤ 2 response at week 16 with SECQ4W vs. placebo in the MLP 37.5% [95% credibility interval (Crl) 20.3-57.2] vs. 23.1% (95% Crl 6.5-49.2) and LPP cohorts [37.5% (95% Crl 20.2-57.3) vs. 30.8% (95% Crl 10.8-57.6)]. In the LPP cohort, a sustained response for IGA ≤ 2 from week 16 to week 32 was achieved with SECQ4W (week 16, 37.5%; week 32, 45.8%), and a substantial improvement was observed in IGA ≤ 2 response in patients from this cohort who switched from placebo (week 16, 30.8%) to SECQ2W after week 16 (week 32, 63.6%). The safety profile was consistent with the known profile of secukinumab and showed no new or unexpected signals. CONCLUSIONS: PRELUDE is the first randomized controlled basket trial evaluating interleukin (IL)-17A inhibition with secukinumab across three subtypes of LP. Secukinumab was well tolerated and safe, showing different response rates across the three subtypes, with numerical IGA improvements in MLP and LPP, and no response in CLP. The study raises the question of a differential role of IL-17A across LP subtypes. The novel IGA score showed significant correlation with both patient- and physician-reported outcome measurements.
EVALuna2:569075

Secukinumab in Pediatric Patients with Plaque Psoriasis: Pooled Safety Analysis from Two Phase 3 Randomized Clinical Trials - Sticherling, Michael; Nikkels, Arjen F.; Hamza, Ashraf M.; Kwong, Pearl; Szepietowski, Jacek C.; El Sayed, Mahira; Ghislain, Pierre Dominique; Khotko, Alkes A.; Patekar, Manmath; Ortmann, Christine Elke; Forrer, Pascal; Papanastasiou, Philemon; et al. (American Journal of Clinical Dermatology, 2023)
Background: Plaque psoriasis affects 1% of the pediatric population, negatively impacting quality of life. The efficacy and safety of secukinumab in pediatric patients with moderate to severe or severe chronic plaque psoriasis have been established in two pivotal phase 3 trials (open-label, NCT03668613; double-blind, NCT02471144). Objectives: The aims were to report the pooled safety of secukinumab up to 52 weeks from two studies in subgroups of pediatric patients stratified by age and bodyweight, and to present, alongside the pediatric data, the pooled safety data from four pivotal adult secukinumab trials. Methods: The safety of secukinumab was evaluated in subgroups of pediatric patients defined by age (6 to < 12 and 12 to < 18 years) and bodyweight (< 25 kg, 25 to < 50 kg, and ≥ 50 kg) in the pooled population. Patients received secukinumab low dose (LD; 75/75/150 mg), secukinumab high dose (HD; 75/150/300 mg), placebo, or etanercept (0.8 mg/kg). For safety analyses, data were pooled from the pediatric studies NCT03668613 and NCT02471144, and presented alongside the pooled data from four adult pivotal studies (NCT01365455, NCT01636687, NCT01358578, NCT01555125). Results: A total of 198 pediatric patients (overall exposure: 184.6 patient-years [PY]) and 1989 adult patients (1749.5 PY) receiving secukinumab up to week 52 were included in this analysis. At week 52, the incidence of adverse events (AEs) was lower in the lower age and bodyweight subgroups. The AEs reported within these subgroups were consistent with the overall AEs reported in this analysis. Overall, exposure-adjusted incidence rates for treatment-emergent AEs were lower in the secukinumab-treated pediatric pool (198.8/100 PY) compared with the etanercept (266.3/100 PY) and adult pools (256.1/100 PY). Up to 52 weeks, the incidence rates of the AEs in the secukinumab-treated patients in the 6 to < 12 years subgroup and 12 to < 18 years subgroup were 167.7/100 PY and 214.7/100 PY, respectively. Similarly, incidence rates of the AEs in the secukinumab-treated patients in the < 25 kg, 25 kg to < 50 kg, and ≥ 50 kg subgroups were 177.3/100 PY, 192.5/100 PY, and 206.8/100 PY, respectively. Nasopharyngitis was the most frequently reported AE in secukinumab-treated pediatric patients across age (< 12 years: 11.8/100 PY; ≥ 12 years: 42.4/100 PY) and bodyweight (< 25 kg: 22.8/100 PY; 25 kg to < 50 kg: 19.0/100 PY; ≥ 50 kg: 43.0/100 PY). Of the 198 secukinumab-treated pediatric patients, one reported nail Candida, one reported skin Candida, and two reported vulvovaginal Candida. Transient and mostly mild events of neutropenia were observed with secukinumab, none leading to study treatment discontinuation. No incidence of treatment-emergent anti-drug antibodies was reported in pediatric patients treated with secukinumab. Conclusions: Secukinumab was well tolerated in pediatric patients with moderate to severe and severe plaque psoriasis across age and bodyweight subgroups. The overall safety profile of secukinumab in pediatric patients was consistent with that of adult patients. ClinicalTrials.gov Identifier: NCT03668613 (Novartis Study Code CAIN457A2311, referred to as A2311), actual study start date: August 29, 2018; actual primary completion date: September 19, 2019; estimated study completion date: September 14, 2023. NCT02471144 (Novartis Study Code CAIN457A2310, referred to as A2310), study start date: September 29, 2015; primary completion date: December 13, 2018; estimated study completion date: March 31, 2023.
CRIS-Team Scopus Importer:2023-07-07

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without previous Systemic Therapy for Improvement of Skin Symptoms: PASI and IGA mod. 2011-Results of the PRIME Study - Reich, K.; Mrowietz, U.; Augustin, M.; Thaci, D.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34358

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without prior System Therapy with regard to compatibility-related Therapeutic Adherence: Safety Results of the PRIME Study - Mrowietz, U.; Augustin, M.; Thaci, D.; Reich, K.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34361

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without prior System Therapy with respect to the Improvement of quality of life: DLQI and SF-36 Results of the PRIME Study - Augustin, M.; Thaci, D.; Reich, K.; Mrowietz, U.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34359

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis with without previous Systemic Therapy for Improvement of Nail Symptoms: NAPSI Results PRIME Study - Thaci, D.; Reich, K.; Mrowietz, U.; Augustin, M.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34360

Secukinumab is superior to fumaric acid esters in treating patients with moderate-to-severe plaque psoriasis who are naive to systemic treatments: results from the randomized controlled PRIME trial - Sticherling, Michael; Mrowietz, U.; Augustin, M.; Thaci, D.; Melzer, N.; Hentschke, C.; Kneidl, J.; Sieder, C.; Reich, K. (British Journal of Dermatology, 2017)
BACKGROUND: Secukinumab is a fully human antibody that neutralizes interleukin-17A. It has significant efficacy and a favourable safety profile in moderate-to-severe plaque psoriasis and psoriatic arthritis. OBJECTIVES: To compare secukinumab with fumaric acid esters (FAEs) in a randomized controlled trial. METHODS: In this 24-week, randomized, open-label, multicentre study with blinded assessment, patients with moderate-to-severe plaque psoriasis, naive to systemic treatments, were randomized to receive secukinumab 300 mg subcutaneously or oral FAEs. The primary end point was ≥ 75% improvement from baseline Psoriasis Area and Severity Index score (PASI 75 response) at week 24, and missing patients were considered responders if they were responders at the time of dropout. RESULTS: In total 202 patients were randomized and 200 were treated with at least one dose. Outcomes at week 24 were available for 147 and imputed for 53 patients. Discontinuations were mostly due to adverse events, which occurred more frequently in the FAE group (1·9% vs. 33·0%). At week 24, significantly more patients receiving secukinumab compared with FAEs achieved PASI 75 response (89·5% vs. 33·7%, P < 0·001), PASI 90 response (81·0% vs. 28·4%, P < 0·001) and Dermatology Life Quality Index 0 or 1 response (71·4% vs. 25·3%, P < 0·001). CONCLUSIONS: Secukinumab demonstrated superior efficacy to FAEs in patients with psoriasis over a 24-week period.
EVALuna2:34340

Secukinumab leads to shifts from stage-based towards response-based disease clusters-comparative data from very early and established psoriatic arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2020)
Background: Limited information exists about the very early forms of psoriatic arthritis. In particular, differences and responsiveness of patient-reported outcomes (PROs) in very early as compared to established PsA have not been investigated to date. Methods: Cross-sectional and prospective longitudinal evaluation of PROs related to pain (VAS), physical function (HAQ-DI, SF-36 physical), mental function (SF-36 mental), impact of psoriatic skin (DLQI), joint (PsAID), and global disease (VAS) in two small prospective observational studies on secukinumab 300 mg over 6 months in very early disease patients (IVEPSA study, N = 20) and established PsA (PSARTROS study, N = 20). Cluster analysis was performed at baseline and 24-weeks of follow-up. Results: While responses in pain and physical activity-related PROs to secukinumab were more pronounced in established PsA than a very early disease, effects on PROs related to general health perception, as well as those related to emotional and mental well-being, were modified in a similar way in very early disease and established PsA. Cluster analysis based on global disease activity and PROs showed that baseline clusters reflected very early disease and established PsA, while after secukinumab treatment these clusters were abolished and new clusters based on differential responses to physically and mentally oriented PROs formed. Conclusions: Inhibition of IL-17A by secukinumab leads to comprehensive improvement of general health perception and mental well-being in very early and established PsA, while overall responses in pain and physical activity are more pronounced in established disease. Most importantly, treatment restructures the original patients' clusters based on disease stage and leads to the formation of new clusters that reflect their response in physical and mental-orientated PROs. Trial registration: NCT02483234, registered 26 June 2015, retrospectively registered.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Cluster analysis; IL-17A; Psoriatic arthritis; Quality of life; Secukinumab

Secukinumab Treatment of moderate to severe Plaque Psoriasis in the clinical Routine Care: Baseline Data from the PROSPECT Study on Psoriasis Pre-treatment - Von Kiedrowski, R.; Korber, A.; Kraehn-Senftleben, G.; Sticherling, Michael; Lange, L.; Bachhuber, T.; Kasparek, T. R.; Augustin, M.; Thaci, D.; Amon, U. (2017)
EVALuna2:34357

Serum autoantibody reactivity in bullous pemphigoid is associated with neuropsychiatric disorders and the use of antidiabetics and antipsychotics: a large, prospective cohort study - Dikmen, H. O.; Yilmaz, K.; Benoit, S.; Bernard, P.; Drenovska, Kossara; Gerdes, S.; Glaeser, R.; Günther, Claudia; Homey, B.; Horvath, O. N.; Huilaja, L.; Joly, P.; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: Bullous pemphigoid (BP), the by far most frequent autoimmune blistering skin disease (AIBD), is immunopathologically characterized by autoantibodies against the two hemidesmosomal proteins BP180 (collagen type XVII) and BP230 (BPAG1 or dystonin). Several comorbidities and potentially disease-inducing medication have been described in BP, yet a systematic analysis of these clinically relevant findings and autoantibody reactivities has not been performed. Objective: To determine associations of autoantibody reactivities with comorbidities and concomitant medication. Methods: In this prospective multicenter study, 499 patients diagnosed with BP in 16 European referral centers were included. The relation between anti-BP180 NC16A and anti-BP230 IgG ELISA values at the time of diagnosis as well as comorbidities and concomitant medication collected by a standardized form were analysed. Results: An association between higher serum anti-BP180 reactivity and neuropsychiatric but not atopic and metabolic disorders was observed as well as with the use of insulin or antipsychotics but not with dipeptidyl peptidase-4 (DPP4) inhibitors, inhibitors of platelet aggregation and L-thyroxine. The use of DPP4 inhibitors was associated with less anti-BP180 and anti-BP230 reactivity compared with BP patients without these drugs. This finding was even more pronounced when compared with diabetic BP patients without DPP4 inhibitors. Associations between anti-BP180 and anti-BP230 reactivities were also found in patients using insulin and antipsychotics, respectively, compared with patients without this medication, but not for the use of inhibitors of platelet aggregation, and L-thyroxine. Conclusion: Taken together, these data imply a relation between autoantibody reactivities at the time of diagnosis and both neuropsychiatric comorbidities as well as distinct concomitant medication suggesting a link between the pathological immune mechanisms and clinical conditions that precede the clinically overt AIBD.
CRIS-Team Scopus Importer:2022-07-22

Serum extracellular matrix biomarkers in rheumatoid arthritis, psoriatic arthritis and psoriasis and their association with hand function - Port, Helena; Coppers, Birte; Tragl, Sonja; Manger, Eva; Niemiec, Lisa Maria; Bayat, Sara; Simon, David; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne Christine; Tascilar, Koray; Hueber, Axel; et al. (Scientific Reports, 2025)
Inflammatory arthritis, including rheumatoid arthritis and psoriatic arthritis, is characterized by physical function impairment. This becomes apparent even before arthritis onset, as in psoriasis (PsO). Chronic inflammation triggers an accelerated remodeling of the extracellular matrix (ECM), resulting in released ECM fragments detectable in blood. We aimed to investigate levels of blood-based ECM biomarkers in patients with RA, PsA, PsO, and healthy controls and to explore the association of ECM biomarkers with hand function impairments. Patients with RA (n = 85), PsA (n = 115), PsO (n = 102) and controls (n = 110) were included in this cross-sectional study. ECM catabolic (C1M, C2M, C3M, C4M, PRO-C4, C6M, ARG), formation (PRO-C1, PRO-C3, PRO-C6) and inflammation biomarkers (VICM) were measured in serum from all patients. Objective hand function (fine motor skills (Moberg-Picking-Up Test), isometric grip strength (dynamometer) and patient-perceived hand function (Michigan Hand Questionnaire (MHQ)) were assessed. Patients with RA and PsA received treatment with disease-modifying anti-rheumatic drugs. VICM levels were higher in RA, PsA, and PsO than in controls (p < 0.0001). PsA and PsO showed higher C4M levels compared to controls (p < 0.0001, p < 0.0001), while C6M was lower in patients with RA, PsA and PsO than in controls (p < 0.0001, p < 0.001, p < 0.01). PsO presented with higher levels of C1M compared to controls and to RA (p < 0.001 and p < 0.0001). PRO-C6 correlated negatively with MHQ (ρ = -0.39, p < 0.01) and grip strength (ρ = -0.31, p < 0.05) in PsO, while only weak correlations were observed between biomarkers and hand function scores for RA and PsA patients (all ρ < ± 0.2–0.3). Patients with RA, PsA, and PsO showed significant alterations in ECM remodeling biomarkers. Especially PsA and PsO had higher levels of inflammatory biomarkers compared to RA and controls, likely due to modulation by treatment. Predominantly in PsO, ECM formation biomarkers were associated with hand function impairments.<br
Keywords: Extracellular matrix; Biochemical markers; Rheumatoid arthritis; Psoriatic arthritis; Psoriasis; Hand function

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ACR Open Rheumatology, 2020)
ObjectiveThe objective of this study was to compare the impact of psoriatic disease (psoriatic arthritis [PsA] and psoriasis) and rheumatoid arthritis (RA) on objective and subjective parameters of hand function.
CRIS-Team WoS Importer:2021-07-16

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Simultaneous quantification of bone erosions and enthesiophytes in the joints of patients with psoriasis or psoriatic arthritis - effects of age and disease duration - Simon, David; Kleyer, Arnd; Faustini, Francesca; Englbrecht, Matthias; Haschka, Judith; Berlin, Andreas; Kraus, Sebastian; Hueber, Axel; Kocijan, Roland; Sticherling, Michael; Rech, Jürgen; Schett, Georg (Arthritis Research & Therapy, 2018)
BACKGROUND: Comprehensive simultaneous quantification of bone erosion and enthesiophytes in the joints of patients with psoriatic arthritis (PsA) has not been performed. Herein, we aimed to compare the extent of bone erosion and enthesiophytes in patients with PsA, psoriasis (PSO) and healthy controls, assess the influence of age and disease duration on the development of erosions and enthesiophytes and define their impact on physical function. METHODS: Patients with PsA or with PSO and controls were analysed by high-resolution peripheral quantitative computed tomography (HR-pQCT). The extent of bone erosions and enthesiophytes was assessed and plotted according to different categories of age, duration of PSO and duration of PsA, respectively. In addition, demographic and disease-specific data, including physical function (health assessment questionnaire) were collected. RESULTS: A total of 203 patients were analysed; 101 had PsA, 55 had PSO and 47 were healthy individuals. Patients with PsA had significantly more and larger erosions (p = 0.002/p = 0.003) and enthesiophytes (p < 0.001) compared to patients with PSO and healthy controls. Patients with PSO and healthy controls did not differ in erosions, while enthesiophytes were more frequent in patients with PSO than in healthy controls. Bone erosions, but not enthesiophytes, showed strong age-dependency in all three groups. In contrast, enthesiophytes were mostly influenced by the duration of PSO and PsA and, in contrast to bone erosions, were associated with poorer physical function. CONCLUSIONS: Bone erosions are age-dependent, enhanced in PsA and increase with disease duration. Enthesiophytes are less age-dependent, are enhanced in both PSO and PsA and strongly influenced by disease duration. Enthesiophytes impact physical function in PsA suggesting the need for early therapeutic interventions to prevent damage.
EVALuna2:34666

Skin and Soft Tissue Infections Caused by Mycobacterium chelonae: More Common Than Expected? - Uslu, Ugur; Boehm, Olga; Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2019)
Mycobacterium chelonae is a rapidly growing non-tuberculous mycobacterium, which causes infections of the human skin and soft tissue. Despite an increasing incidence of such infections, patients are often misdiagnosed. We report here 5 patients with cutaneous and/or soft tissue infection due to M. chelonae who were diagnosed and treated at our centre. Two of the 5 patients were on immunosuppressive treatment. While clinical presentations differed in each patient, all had a long history of skin lesions. In addition to careful history-taking, tissue biopsies were obtained for mycobacterial culture and histopathological examination. Culture-directed antibiotic therapy was initiated, which resulted in a slow, but continuous, healing of the lesions. In summary, M. chelonae infections are still relatively rare, but should be considered in both immunocompromised and immunocompetent patients with prolonged skin lesions resistant to standard antibiotic treatment. For diagnosis, tissue analysis for mycobacterial culture and histopathological examination, and once diagnosed, adequate antibiotic treatment, is needed.
CRIS-Team WoS Importer:2019-09-10

Skin lesions may be misleading for final diagnosis – a case of delayed diagnosis and therapy - Meder, Christine; Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-06-09
Keywords: bacterial infections; T cell; virus

Sklerosierende Hauterkrankungen - Sticherling, Michael (Internist, 2019)
Sclerosing skin manifestations are more a symptom than a diagnosis and must therefore be meticulously clarified. Systemic scleroderma as a multiorgan disease must be distinguished from localized scleroderma or morphea because in addition to a different clinical picture they have a different prognosis and necessitate other therapeutic procedures. Rare sclerosing skin diseases with implications for internal medicine are eosinophilic fasciitis, Buschke’s scleredema adultorum, scleromyxedema and nephrogenic systemic fibrosis.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Mixed connective tissue disease; Morphea; Scleredema adultorum; Scleromyxedema; Systemic scleroderma

Specific dermatoses of pregnancy - Ambros-Rudolph, C. M.; Sticherling, Michael (Hautarzt, 2017)
The specific dermatoses of pregnancy represent a heterogeneous group of inflammatory skin diseases related to pregnancy and/or the postpartum period. A clinically relevant classification has been well established over the past 10 years and includes pemphigoid gestationis, polymorphic eruption of pregnancy, intrahepatic cholestasis of pregnancy, and atopic eruption of pregnancy. The hallmark of all four entities is severe pruritus that is accompanied by characteristic skin changes. While some of these dermatoses are distressing only to the mother because of pruritus, others may be associated with significant fetal risks. Early diagnosis and prompt treatment are therefore essential. In this review, we discuss in detail pemphigoid gestationis, polymorphic and atopic eruptions of pregnancy whereas intrahepatic cholestasis of pregnancy is discussed in a separate article (Kremer A, Ständer S, DOI 10.1007/s00105-016-3923-y ). Furthermore, we present a helpful algorithm for diagnosis and management of pruritus in pregnancy.
EVALuna2:34362

Status report on the atopic dermatitis registry TREATgermany Statusbericht zum Neurodermitisregister TREATgermany - Siegels, D.; Haufe, E.; Heinrich, L.; Werfel, T.; Weidinger, S.; Schmitt, Jochen; Abraham, S.; Asefi, M.; Asmussen, Andrea; Augustin, M.; Bell, Magnus; Bieber, T.; et al. (Allergologie, 2021)
CRIS-Team Scopus Importer:2021-10-22
Keywords: Atopic dermatitis; Atopic eczema; Clinical registry; Clinical symptom severity; Systemic treatment

STRUCTURAL ENTHESEAL LESIONS IN PSORIASIS PATIENTS ARE ASSOCIATED WITH AN INCREASED RISK OF PROGRESSION TO PSORIATIC ARTHRITIS - A PROSPECTIVE COHORT STUDY - Simon, David; Tascilar, K.; Kleyer, Arnd; Bayat, Sara; Kampylafka, E.; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, K.; Sticherling, Michael; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Subclinical joint inflammation in patients with psoriasis without concomitant psoriatic arthritis: a cross-sectional and longitudinal analysis - Faustini, Francesca; Simon, Dominic; Oliveira, Isabelle; Kleyer, Arnd; Haschka, Judith; Englbrecht, Matthias; Cavalcante, Alan Rodrigues; Kraus, Sebastian; Tabosa, Taiane Ponte; Figueiredo, Camille; Hueber, Axel; Kocijan, Roland; et al. (Annals of the Rheumatic Diseases, 2016)
To search for subclinical inflammatory joint disease in patients with psoriasis without psoriatic arthritis (PsA), and to determine whether such changes are associated with the later development of PsA.Eighty-five subjects without arthritis (55 with psoriasis and 30 healthy controls) received high field MRI of the hand. MRI scans were scored for synovitis, osteitis, tenosynovitis and periarticular inflammation according to the PsAMRIS method. Patients with psoriasis additionally received complete clinical investigation, high-resolution peripheral quantitative CT for detecting erosions and enthesiophytes and were followed up for at least 1 year for the development of PsA.47% of patients with psoriasis showed at least one inflammatory lesion on MRI. Synovitis was the most prevalent inflammatory lesion (38%), while osteitis (11%), tenosynovitis (4%) and periarticular inflammation (4%) were less frequent. The mean (±SD) PsAMRIS synovitis score was 3.0±2.5 units. Enthesiophytes and bone erosions were not different between patients with psoriasis with or without inflammatory MRI changes. The risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia, but only 13% if patients had normal MRIs and did not report arthralgia.Prevalence of subclinical inflammatory lesions is high in patients with cutaneous psoriasis. Arthralgia in conjunction with MRI synovitis constitutes a high-risk constellation for the development of PsA.
EVALuna2:13265

SUBJECTIVE ASSESSMENT OF PHYSICAL FUNCTION DOES NOT SUFFICIENTLY EXPLAIN VARIANCE OF MEASURED HAND FUNCTION AND GRIP STRENGTH IN ARTHRITIS PATIENTS AND NON-ARTHRITIS CONTROLS - Liphardt, Anna-Maria; Tascilar, Koray; Coppers, Birte; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Bayat, Sara; Simon, David; Sticherling, Michael; Rech, Jürgen; Hueber, A.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Successful treatment of refractory palmoplantar psoriasis in a psoriatic arthritis patient with the JAK inhibitor tofacitinib - Valor-Mendez, Larissa; Sticherling, Michael; Kleyer, Arnd; Schett, Georg (Clinical and Experimental Rheumatology, 2021)
CRIS-Team WoS Importer:2021-03-26

Successful treatment of ulcerative necrobiosis lipoidica with JAK inhibitor - Erfurt-Berge, Cornelia; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2020)
Necrobiosis lipoidica (NL) is a rare granulomatous disease that predominantly affects middle aged women and is often associated with diabetes mellitus and other metabolic disorders 1 . About 30 % of the patients develop ulcerations within NL lesions on the lower leg, which complicate the course of disease and are often recalcitrant to standard wound care procedures 2 . Systemic therapies for NL are reported only for single cases or in small case series with varying outcome 3 . Randomized controlled trials are missing due to the character of NL as an orphan disease.
EVALuna2:212858

Systemic sclerosis - the dermatological perspective - Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Systemic scleroderma/systemic sclerosis (SSc) is an inflammatory connective tissue disease clinically characterized by two major subtypes: limited and diffuse SSc. While both conditions present with Raynaud's phenomenon (paroxysmal digital ischemia), diffuse SSc is associated with rapid disease progression and early - prognostically relevant - involvement of internal organs. Treatment is challenging. In addition to general lifestyle modifications, measures include treatments aimed at improving circulation as well as immunosuppressive and immunomodulatory drugs. However, these agents are effective only in terms of slowing disease progression.
CRIS-Team WoS Importer:2019-08-13

Systemic therapy with calcitonin has positive clinical effects on systemic sclerosis in patients with cutaneous manifestations - Uslu, Ugur; Streiff, Laura; Sticherling, Michael (European Journal of Dermatology, 2018)
BACKGROUND: Calcitonin gene-related peptide (CGRP) is a vasodilatory neuropeptide that plays an important role in the blood vessels of heart and peripheral circulation, a lack of which may cause vasculopathies. OBJECTIVE: In this study, the clinical course of disease, as well as the efficacy, side effects, and patient satisfaction of systemic calcitonin therapy in patients with systemic sclerosis (SSc), was evaluated. METHODS: Forty-nine patients received repetitive intravenous calcitonin infusions as first-line treatment. The average number of cycles was 12.2 ± 10.3 over a period of 30 months (each cycle: 100 U/day over 10 days). Clinical examinations, laboratory tests, and organ imaging were performed before the start of, and at regular intervals during therapy in order to evaluate organ manifestations and the clinical course of the disease. In addition, patients' own experiences of the therapy, side effects, and therapy success were evaluated with standardized questionnaires. RESULTS: Over the course of the treatment, seven patients experienced improvements in their condition with a considerable reduction in digital ulceration and improved movement (14.3%). Pulmonary function in seven patients improved during the therapy (14.3%). With regards to side effects, nausea (41.7%), headaches (33.3%), fluctuations in blood pressure (29.2%), and flushing (29.2%) were observed. Overall, 45.8% of patients evaluated the therapy as good and 58.3% would undergo further courses of therapy with calcitonin. CONCLUSIONS: Systemic calcitonin treatment seems to have positive clinical effects on SSc and contributes to relieving symptoms, especially in patients with cutaneous manifestations. No severe side effects were reported during this study.
EVALuna2:34793

Systemische Sklerodermie - die dermatologische Sicht - Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
EVALuna2:212837

Systemtherapie der Neurodermitis und Psoriasis im Kindes- und Jugendalter - Sticherling, Michael (Die Dermatologie, 2025)
Psoriasis and atopic dermatitis are among the most frequent chronic, inflammatory skin diseases of childhood and adolescence. Regarding profound consequences for the physical and psychosocial development of affected patients, a timely and individually adapted therapy has to be initiated, in case of severe disease systemic treatment. Modern, targeted, highly efficient and well-tolerated agents are currently available. Overlapping psoriasis and atopic dermatitis have been appreciated recently, both idiopathic and therapeutically induced. Their prevention or early detection is mandatory for optimal management of patients.
CRIS-Team Scopus Importer:2025-04-04
Keywords: Biological products; Clinical laboratory tests; Janus kinase inhibitors; Paradoxic effects; Psoriasiformic dermatitis

Systemtherapien bei Kindern und Jugendlichen in der Dermatologie - Sticherling, Michael; Süßmuth, Kira (Die Dermatologie, 2025)
CRIS-Team Scopus Importer:2025-04-11

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

The Art of Making Moulages - a hidden Art? - Sticherling, Michael; Groenhardt, K.; Saake, Marc (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

The genetic basis for most patients with pustular skin disease remains elusive - Mössner, R.; Wilsmann-Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J. C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K. P.; et al. (British Journal of Dermatology, 2017)
Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause/ contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP).To better understand the disease-relevance of these genes, we screened our cohorts of patients with pustular skin diseases (primarily GPP and palmoplantar pustular psoriasis [PPP]) for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN.Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients - 61 with GPP, 2 with acute generalized exanthematous pustulosis and 4 with acrodermatitis continua suppurativa Hallopeau. We screened IL36RN and AP1S3 for intragenic copy-number-variants, 258 PPP patients for coding changes in AP1S3. 11 heterozygous IL36RN mutations carriers were analyzed for a 2(nd) non-coding IL36RN mutation. Genotype-phenotype-correlations in carriers/ non-carriers of IL36RN mutations were assessed within the GPP cohort.The majority of patients (GPP:64%) did not carry rare variants in any of the three genes. Bi-allelic and mono-allelic IL36RN mutations were identified in 15 and 5 GPP patients, respectively. Non-coding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype-phenotype-correlation observed for IL36RN mutation carriers was early age of disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutations carriers.The identification of IL36RN mutation carriers harboring additional rare variants in CARD14 or AP1S3, indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest additional disease-causing genetic factors in heterozygous IL36RN mutation carriers outside IL36RN. This article is protected by copyright. All rights reserved.
EVALuna2:9330

THE GERMAN AD REGISTRY TREATGERMANY: RESULTS FROM AN INTERIM DATA ANALYSIS ON BASELINE CHARACTERISTICS, COMORBIDITIES AND TREATMENT HISTORY - Heratizadeh, Annice; Haufe, Eva; Stoelzl, Dora; Abraham, Susanne; Heinrich, Luise; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Augustin, Matthias; Wiemers, Franca; Zink, Alexander; Von Kiedrowski, Ralph; et al. (ACTA DERMATO-VENEREOLOGICA, 2021)
CRIS-Team WoS Importer:2021-05-07

The p.Arg435His Variation of IgG3 With High Affinity to FcRn Is Associated With Susceptibility for Pemphigus Vulgaris-Analysis of Four Different Ethnic Cohorts - Recke, Andreas; Konitzer, Sarah; Lemcke, Susanne; Freitag, Miriam; Sommer, Nele Maxi; Abdelhady, Mohammad; Amoli, Mahsa M.; Benoit, Sandrine; El-Chennawy, Farha; Eldarouti, Mohammad; Eming, Ruediger; Glaeser, Regine; et al. (Frontiers in Immunology, 2018)
IgG3 is the IgG subclass with the strongest effector functions among all four IgG subclasses and the highest degree of allelic variability among all constant immunoglobulin genes. Due to its genetic position, IgG3 is often the first isotype an antibody switches to before IgG1 or IgG4. Compared with the other IgG subclasses, it has a reduced half-life which is probably connected to a decreased affinity to the neonatal Fc receptor (FcRn). However, a few allelic variants harbor an amino acid replacement of His435 to Arg that reverts the half-life of the resulting IgG3 to the same level as the other IgG subclasses. Because of its functional impact, we hypothesized that the p.Arg435His variation could be associated with susceptibility to autoantibody-mediated diseases like pemphigus vulgaris (PV) and bullous pemphigoid (BP). Using a set of samples from German, Turkish, Egyptian, and Iranian patients and controls, we were able to demonstrate a genetic association of the p.Arg435His variation with PV risk, but not with BP risk. Our results suggest a hitherto unknown role for the function of IgG3 in the pathogenesis of PV.
EVALuna2:34784

Therapierefraktäre generalisierte pustulöse Psoriasis – Ein deutsches Problem - Sollfrank, Lukas; Kemenes, Stephan; Voskens, Caroline; Sticherling, Michael (Aktuelle Dermatologie, 2024)
Generalized pustular psoriasis is a rare, potentially life-threatening, autoinflammatory skin disease that is considered a special form of psoriasis vulgaris. The anti-IL-36 receptor antibody spesolimab was recently approved as a targeted treatment option for this disease for the first time. However, the Joint Federal Committee (Gemeinsamer Bundesausschuss) denied this treatment option an additional benefit compared to systemic glucocorticoids, which is why the substance is not on the market in Germany anymore. We report on a 47-year-old female patient who, after months of high-dose glucocorticoid therapy, was successfully treated with spesolimab after final approval by her health insurance company.
CRIS-Team Scopus Importer:2025-07-10
Keywords: generalisierte pustulöse Psoriasis; generalized pustular psoriasis; GPP; IL36

Three generations of suffering: cryopyrin-associated periodic syndrome with NLRP3 mutation in a family - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael Constantin (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-12-24

Topical therapy of psoriasis vulgaris - a treatment pathway - Koerber, Andreas; Wilsmann-Theis, Dagmar; Augustin, Matthias; Von Kiedrowski, Ralph; Mrowietz, Ulrich; Rosenbach, Thomas; Meller, Stephan; Pinter, Andreas; Sticherling, Michael; Gerdes, Sascha (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
In daily practice topical treatment of psoriasis and its subtypes is of high importance. It is standard for the treatment of mild psoriasis and is used to support treatment of moderate-to-severe psoriasis. When optimizing psoriasis treatment not only the choice of suitable compounds, but also the formulation aspect matters. Developments in the latter field were not considered in the 2017 published update of the current S3-guideline on psoriasis. The presented pathway was prepared during a PsoNet speaker conference and confirmed by the national psoriasis care conference. It aims to illustrate current treatment options.
CRIS-Team WoS Importer:2019-05-09

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Travel-associated infectious skin diseases - Rongisch, Robert; Schmidt, Enno; Deresz, Nicolai; Deresz, Katharina; Schoefer, Helmut; Schaekel, Knut; Jakob, Thilo; Maurer, Marcus; Sticherling, Michael; Sunderkoetter, Cord; Babilas, Philipp; Spornraft-Ragaller, Petra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-12

Treatment of moderate-to-severe atopic dermatitis with baricitinib: Results from an interim analysis of the TREATgermany registry - Traidl, Stephan; Heinrich, Luise; Siegels, Doreen; Heratizadeh, Annice; Kind, Barbara; Haufe, Eva; Abraham, Susanne; Schäfer, Thomas; Augustin, Matthias; Harder, Inken; Pinter, Andreas; Schäkel, Knut; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
CRIS-Team Scopus Importer:2024-04-12

Trichophyton mentagrophytes ITS Genotyp VIII/Trichophyton indotineae in Deutschland – Neubewertung nach 5 Jahren - Uhrlaß, Silke; Panzer, Rüdiger; Koch, Daniela; Mütze, Hanna; Richter, Susanne; Müller, Lena; Ardabili, Michael; Averbeck, Marko; Baldauf, Claudia; Batel, Janina; Bender-Säbelkampf, Sophia; Braun, Martin; et al. (Die Dermatologie, 2025)
Trichophyton (T.) mentagrophytes ITS genotype VIII/T. indotineae (TMVIII/TINDO) is a new, anthropophilic dermatophyte from the T. mentagrophytes/T. interdigitale complex that has gained increasing importance worldwide in recent years. This pathogen is characterized by frequent terbinafine resistance and a clinical picture of pronounced, inflammatory, and therapy-resistant dermatophytoses that predominantly affect the groin, trunk, extremities, and face. Between 2018 and the end of 2024, all TMVIII/TINDO cases detected in patients from Germany by culture and/or molecular biology were systematically recorded at the Leipzig–Mölbis laboratory. Identification and genotyping were performed by sequencing the internal transcribed spacer (ITS) region of the rDNA. In vitro resistance testing for terbinafine and itraconazole was performed using a breakpoint test. Additionally, the squalene epoxidase (SQLE) gene was sequenced to analyze resistance-associated point mutations. A total of 242 isolates from 196 patients were identified; some patients were consecutively detected repeatedly. The majority of affected patients had a migration background, particularly from South Asia (especially India) and Arab countries. Only a few infections were diagnosed in patients of German descent. As part of the diagnostic workup an in vitro susceptibility testing was performed using a breakpoint test, which demonstrated terbinafine resistance in 61.8% of the TMVIII/TINDO strains. Point mutations in the SQLE gene that correlated with resistance were found in a total of 161 of 188 strains. The most frequently detected mutation was Phe397Leu, which was associated with terbinafine resistance and clinical treatment failure with terbinafine in all cases. In addition, double mutations were detected in 26 strains. In vitro itraconazole resistance was observed in 11 of 186 tested isolates, corresponding to 5.9%. Itraconazole is currently the drug of choice for the systemic treatment of TMVIII/TINDO dermatophytoses. The recommended dosage is 100 mg twice daily for a period of 4–8 weeks, or up to 12 weeks if needed. Concurrent topical treatment with azoles, amorolfine, or ciclopirox is always recommended. In the event of itraconazole treatment failure, there are currently no standardized treatment recommendations. The off-label use of voriconazole has been reported in isolated cases, and there is also experimental experience with other active ingredients. The spread of TMVIII/TINDO in Germany and worldwide is particularly worrying in view of the dermatophyte’s resistance to terbinafine and itraconazole.
CRIS-Team Scopus Importer:2025-08-29
Keywords: Dermatophyte; Genotyping; Squalene epoxidase; Terbinafine resistance; Tinea corporis

TYPE 3 INNATE LYMPHOID CELLS ARE KEY DRIVERS OF PSORIATIC ARTHRITIS - Raimondo, M. G.; Rauber, S.; Luber, M.; Rigau, A. Rius; Weber, Stefanie; Anchang, Charles Gwellem; Agarwal, Rahul; Soare, A.; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Ulcerative colitis: yet another paradoxical effect of tumour necrosis factor blockers? - Sticherling, Michael (British Journal of Dermatology, 2018)
EVALuna2:34402

Uncommon Presentation of Scleromyxoedema with a Distribution Pattern Mimicking a Photodermatosis - Kirchberger, Michael Constantin; Sticherling, Michael; Erdmann, Michael (Acta Dermato-Venereologica, 2017)
EVALuna2:34345

Unveiling Metabolic Similarities of Entheses in Patients with Psoriasis and Psoriatic Arthritis Using Noninvasive In Vivo Molecular Imaging: Results From a Cross-sectional Exploratory Study - Fagni, Filippo; Tascilar, Koray; Noversa de Sousa, Rita; Bayat, Sara; Sollfrank, Lukas; Kleyer, Arnd; Sticherling, Michael; Regensburger, Adrian; Knieling, Ferdinand; Neurath, Markus; Schett, Georg; Waldner, Maximilian; et al. (Arthritis and Rheumatology, 2024)
Objective: We assessed and compared molecular tissue changes at the entheses in patients with psoriasis (PsO) and psoriatic arthritis (PsA) and in healthy controls (HCs) in vivo using multispectral optoacoustic tomography (MSOT) and described their relationship with clinical and ultrasound findings of enthesitis. Methods: A cross-sectional study (MSOT and Arthrosonography in PsA) in biologic disease-modifying antirheumatic drug–naïve patients with PsA and PsO and HCs was performed. Participants underwent clinical, ultrasonographic, and MSOT examination of six entheses (lateral humeral epicondyle, distal patellar tendon attachment, and Achilles tendon attachment). MSOT-measured hemoglobin (Hb), oxygen saturation (SO2), collagen, and lipid levels were quantified, and mean differences between groups were calculated using linear mixed effects models. MSOT-measured analytes were compared between entheses with and without clinical and ultrasound anomalies. Results: Ninety participants were included (30 PsO, 30 PsA, and 30 HCs), 540 entheses were clinically assessed, and 540 ultrasound and 830 MSOT scans were obtained. Patients with PsA and PsO showed increased oxygenated Hb (PsA: P = 0.003; PsO: P = 0.054) and SO2 (PsA: P < 0.001; PsO: P = 0.001) levels and decreased collagen signals (PsA: P < 0.001; PsO: P < 0.001) compared with HCs, with more pronounced changes in PsA. Significantly lower collagen levels (P = 0.01) and increased lipids (P = 0.03) were recorded in tender entheses compared with nontender ones. Erosions and enthesophytes on ultrasound were associated with significant differences in SO2 (P = 0.014) and lipid signals (P = 0.020), respectively. Conclusion: Patients with PsA and PsO exhibit an analogous metabolic pattern at the entheses that is exacerbated in the presence of inflammation. These findings support the notion of a psoriatic disease spectrum characterized by common immunometabolic tissue changes.
CRIS-Team Scopus Importer:2024-07-19

Usage and effectiveness of systemic treatments in adults with severe atopic eczema: First results of the German Atopic Eczema Registry TREATgermany - Schmitt, Jochen; Abraham, Susanne; Trautmann, Freya; Stephan, Victoria; Foelster-Holst, Regina; Homey, Bernhard; Bieber, Thomas; Novak, Natalija; Sticherling, Michael; Augustin, Matthias; Kleinheinz, Andreas; Elsner, Peter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
BACKGROUND: The goal of clinical registries is to document the use and effectiveness of therapeutic interventions under real-life conditions. They are an indispensable prerequisite of evidence-based health care. METHODS: Initiated in 2011, the German Atopic Dermatitis Registry TREATgermany is the first registry of patients with severe atopic dermatitis worldwide. Adults with severe atopic dermatitis (current/prior systemic antiinflammatory treatment and/or objective SCORAD ≥ 40) are prospectively followed over the course of 24 months. Employed treatment modalities are documented, and validated measuring tools are used to assess clinical disease severity (EASI, objective SCORAD), quality of life (DLQI), symptoms (POEM), global disease severity, as well as patient satisfaction. Herein, we describe the characteristics, therapeutic selection, and effectiveness of systemic antiinflammatory treatments of patients enrolled in the registry until October 2014. RESULTS: Overall, 78 individuals (mean age 39 years, 61 % men) were enrolled at five recruitment centers. Patients frequently made use of inpatient and outpatient services. Not only was cyclosporine the most frequently administered systemic treatment, but also the most effective (EASI 50 response rate 51 %; EASI 75 response rate 34 % at 12 weeks). Azathioprine, methotrexate, oral prednisolone, mycophenolate, alitretinoin, and leflunomide were also used in some patients. CONCLUSIONS: The present analysis of the German Atopic Dermatitis Registry provides important data with respect to current medical care of adults with severe atopic dermatitis in Germany. It shows the high disease burden, the benefits of current treatment options, and the need for additional effective and safe long-term treatment options.
EVALuna2:34363

Vasoactive Therapy in Systemic Sclerosis: Real-life Therapeutic Practice in More Than 3000 Patients - Moinzadeh, Pia; Riemekasten, Gabriela; Siegert, Elise; Fierlbeck, Gerhard; Henes, Joerg; Blank, Norbert; Melchers, Inga; Mueller-Ladner, Ulf; Frerix, Marc; Kreuter, Alexander; Tigges, Christian; Lahner, Nina; et al. (Journal of Rheumatology, 2016)
Vasculopathy is a key factor in the pathophysiology of systemic sclerosis (SSc) and the main cause for Raynaud phenomenon (RP), digital ulcers (DU), and/or pulmonary arterial hypertension (PAH). It is so far unknown how patients with SSc are treated with vasoactive agents in daily practice. To determine to which extent patients with SSc were treated with different vasoactive agents, we used data from the German Network for Systemic Scleroderma registry.The data of 3248 patients with SSc were analyzed.Patients were treated with vasoactive drugs in 61.1% of cases (1984/3248). Of these, 47.6% received calcium channel inhibitors, followed by 34.2% treated with angiotensin-converting enzyme (ACE) inhibitors, 21.1% treated with intravenous (IV) prostanoids, 10.1% with pentoxifylline, 8.8% with angiotensin 1 receptor antagonists (AT1RA), 8.7% with endothelin 1 receptor antagonists (ET1RA), 4.1% with phosphodiesterase type 5 (PDE5) inhibitors, and 5.3% with others. Patients with RP received vasoactive therapy in 63.3% of cases, with DU in 70.1%, and with PAH in 78.2% of cases. Logistic regression analysis revealed that patients with PAH were significantly more often treated with PDE5 inhibitors and ET1RA, and those with DU with ET1RA and IV prostanoids. In addition, 41.8% of patients were treated with ACE inhibitors and/or AT1RA. Patients registered after 2009 received significantly more often ET1RA, AT1RA, and IV prostanoids compared with patients registered prior to 2005.These data clearly indicate that many patients with SSc do not yet receive sufficient vasoactive therapy. Further, in recent years, a marked change of treatment regimens can be observed.
EVALuna2:13183

VEXAS syndrome mimicking lupus-like disease - Valor-Mendez, Larissa; Sticherling, Michael; Zeschick, Martin; Atreya, Raja; Schmidt, Daniela; Waldfahrer, Frank; Saake, Marc; Hüffmeier, Ulrike; Schett, Georg; Rech, Jürgen (Rheumatology, 2023)
CRIS-Team WoS Importer:2023-03-17

Wahrnehmung der Corona-Pandemie durch Neurodermitispatienten – Ergebnisse aus dem Neurodermitisregister TREATgermany - Helmert, Claudia; Siegels, Doreen; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Kleinheinz, Andreas; Harder, Inken; Schäkel, Knut; Effendy, Isaak; Wollenberg, Andreas; Sticherling, Michael; Stahl, Maren; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-02-04

Zinc deficiency-associated dermatitis in a prematurely born infant - Grötsch, Jennifer; Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
CRIS-Team Scopus Importer:2025-02-14